Contact lens with hydrogel coating thereon
By forming a crosslinked hydrogel coating on the contact lens precursor, the complex process of preparing water gradient contact lenses in the prior art is solved, and the high hydrophilicity and lubricity of the lens surface is achieved, and the manufacturing process is simplified.
Patent Information
- Application Number
- CN202380053885.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-17
- Filing Date
- 2023-08-16
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art requires additional steps to produce partially crosslinked and thermally crosslinkable hydrophilic polymer materials in the preparation of water gradient contact lenses, resulting in complex manufacturing processes.
By immersing the contact lens precursor in an aqueous solution containing a hydrophilic copolymer and heating at high temperatures, a crosslinked hydrogel coating is formed, which is attached to the lens surface through a covalent bond between the carboxylic acid group and the epoxy group.
The manufacturing process of preparing water gradient contact lenses is simplified, the hydrophilicity and lubricity of the lens surface are improved, and the lens has a water rupture time of at least 10 seconds.
Smart Images

Figure CN119731560A_ABST
Abstract
Description
[0001] The present invention generally relates to a cost-effective and time-saving method for applying a hydrogel coating to a contact lens, particularly a silicone hydrogel contact lens, to improve its hydrophilicity and lubricity. In addition, the present invention provides an ophthalmic lens product. Background Art
[0002] In recent years, many attempts have been made to develop contact lenses with improved wearing comfort.
[0003] One example is the incorporation of leachable wetting agents into contact lenses (see, e.g., U.S. Pat. Nos. 4,045,547, 4,042,552, 5,198,477, 5,219,965, 6,367,929, 6,822,016, 7,279,507, 8,030,369, and 9,804,295).
[0004] Another example is the incorporation of bioactive agents and hydrophobic comfort agents into contact lenses (see, e.g., U.S. Pat. No. 10,155,349).
[0005] Another example is the preparation of contact lenses with nanotextured surfaces that mimic the surface texture of the human cornea (see, e.g., U.S. Pat. No. 9,244,195).
[0006] In addition, another example is the development of a new class of soft contact lenses, water gradient contact lenses. This new class of soft contact lenses has been first used as daily disposable contact lenses. (Alcon) developed and successfully introduced to the market. Weekly or monthly disposable water gradient soft contact lenses have also been developed (US11256003) and used as monthly replacement water gradient contact lenses. (Alcon Corporation) introduced into the market these water gradient soft contact lenses have a durable hydrogel coating and have reduced absorption of positively charged antimicrobial agents present in multi-use lens care solutions. This new class of soft contact lenses is characterized by having a water gradient structural configuration, an increase in water content observed from the core to the surface of the contact lens, with the highest water content being achieved in the area near and including the surface of the contact lens (see US 8480227). This unique design can provide a highly lubricated and very soft, water-rich lens surface, thereby providing patients with superior wearing comfort.
[0007] As described in US 8480227 and US 11256003, methods for preparing water gradient contact lenses generally involve forming a non-silicone hydrogel coating on a contact lens using a partially crosslinked and thermally crosslinkable hydrophilic polymer material. These methods may require additional steps for producing the partially crosslinked and thermally crosslinkable hydrophilic polymer material. Therefore, it is desirable to eliminate such additional steps to simplify the manufacturing method for preparing water gradient contact lenses. Summary of the invention
[0008] In one aspect, the present invention provides a method for preparing a coated contact lens, the method comprising the steps of: (1) obtaining a contact lens precursor having a concave surface and an opposite convex surface and comprising a lens bulk material and carboxylic acid groups on and / or near the anterior and posterior surfaces; (2) immersing the contact lens precursor in an aqueous solution in a container, wherein the aqueous solution comprises from about 0.01% to about 5.0% by weight of at least one hydrophilic copolymer, the hydrophilic copolymer comprising (a) monomer units of at least one vinyl monomer containing an epoxy group, (b) monomer units of at least one vinyl monomer containing an amino group having a primary or secondary amino group, (c) at least one polyethylene glycol-containing monomer The invention relates to a method of coating a contact lens having a hydrogel coating on a front surface and a back surface thereof, wherein the hydrogel coating comprises a cross-linked polymer material comprising polymer chains derived from the hydrophilic copolymer.
[0009] In another aspect, the present invention provides a contact lens, preferably a silicone hydrogel contact lens, comprising an anterior surface, an opposite posterior surface, and a layered structural configuration from the anterior surface to the posterior surface, wherein the layered structural configuration comprises an outer anterior surface hydrogel layer, an inner layer, and an outer posterior surface hydrogel layer, wherein the inner layer is a lens bulk material, wherein the outer anterior surface hydrogel layer and the outer posterior surface hydrogel layer comprise a cross-linked polymer material, wherein the cross-linked polymer material comprises polymer chains derived from a hydrophilic copolymer, wherein the hydrophilic copolymer comprises (a) monomer units of at least one vinyl monomer containing an epoxy group, (b) b) monomer units of at least one amino group-containing vinyl monomer having a primary or secondary amino group, (c) monomer units of at least one vinyl monomer containing polyethylene glycol, and (d) monomer units of at least one vinyl monomer containing phosphorylcholine, wherein the sum of the amounts of components (a) and (b) in the at least one hydrophilic copolymer is about 40% or less by mole, wherein the outer front surface hydrogel layer and the surface hydrogel layer are covalently attached to the inner layer through bonds each formed between one carboxylic acid group and one epoxy group, wherein the contact lens has a water break up time (WBUT) of at least 10 seconds.
[0010] These and other aspects of the invention (including various preferred embodiments in any combination) will become apparent from the following description of the presently preferred embodiments. The detailed description is merely illustrative of the invention and does not limit the scope of the invention, which is defined by the appended claims and their equivalents. As should be apparent to those skilled in the art, many variations and modifications of the invention may be implemented without departing from the spirit and scope of the novel concepts disclosed herein. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 A cross-sectional view schematically depicts the structural configuration of a contact lens according to a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0012] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the invention belongs. In general, the nomenclature and laboratory procedures used herein are well known in the art and commonly used. Conventional methods are used for these procedures, such as those provided in the art and various general references. When a term is provided in the singular, the inventors also contemplate the plural form of the term. The nomenclature used herein and the laboratory procedures described below are well known in the art and commonly used.
[0013] In this application, "about" as used herein means that the number referred to as "about" includes the recited number plus or minus 1%-10% of the recited number.
[0014] “Optional” or “optionally” means that the subsequently described event or circumstance may or may not occur, and means that the description includes instances where the event or circumstance occurs and instances where it does not.
[0015] "Contact lens" refers to a structure that can be placed on or in the wearer's eye. Contact lenses can correct, improve, or change the user's vision, but do not necessarily do so. Contact lenses can be any suitable material known in the art or later developed, and can be hard lenses, rigid gas permeable lenses, soft lenses, or hybrid lenses.
[0016] The terms "front surface," "front surface," "front curve surface," or "FC surface" as used herein with respect to contact lenses interchangeably refer to the surface of the contact lens facing away from the eye during wear. The front surface (FC surface) is typically substantially convex.
[0017] "Posterior surface," "back surface," "base curve surface," or "BC surface" as used in this application with respect to contact lenses interchangeably means the surface of the contact lens that faces the eye during wear. The posterior surface (BC surface) is typically substantially concave.
[0018] "Hard contact lenses" refer to contact lenses that contain a hard plastic (eg, polymethyl methacrylate) as the lens body (or so-called "core") material.
[0019] A "rigid gas permeable contact lens" refers to a contact lens that comprises a gas permeable material (eg, a material made from fluorosilicone acrylate) as the lens body (or so-called "core") material.
[0020] Soft contact lenses can be non-silicone hydrogel contact lenses or silicone hydrogel contact lenses. "Non-silicone hydrogel contact lenses" refer to contact lenses that contain a non-silicone hydrogel bulk (or so-called "core") material. "Silicone hydrogel contact lenses" or "SiHy" interchangeably refer to contact lenses that contain a silicone hydrogel bulk (or so-called "core") material.
[0021] The hybrid contact lens includes a lens body material consisting essentially of a central optical zone made of a gas permeable lens material and a peripheral zone made of a silicone hydrogel or conventional hydrogel lens material and extending outwardly from and surrounding the central optical zone.
[0022] The embedded contact lens comprises a lens body material consisting essentially of a 3-dimensional embedded article and a non-silicone hydrogel material or a silicone hydrogel material, wherein the 3-dimensional embedded article is made of a non-hydrogel material and has a smaller 3-dimensional size than the contact lens, so that it is partially or preferably completely embedded in the non-silicone hydrogel material or the silicone hydrogel material. The non-hydrogel material can be any material that absorbs less than 10% (preferably about 7.5% or less, more preferably about 5.0% or less, even more preferably about 2.5% or less) of water by weight when fully hydrated.
[0023] "Hydrogel" or "hydrogel material" refers to a cross-linked polymer material that is insoluble in water but is capable of holding at least 10 weight percent water in its three-dimensional polymer network (ie, polymer matrix) when fully hydrated.
[0024] As used in this application, the term "non-silicone hydrogel" refers to a hydrogel that theoretically does not contain silicone.
[0025] Siloxanes, which are often also described as silicones, refer to molecules having at least one —Si—O—Si— moiety, wherein each Si atom carries two organic groups as substituents.
[0026] As used in this application, the term "silicone hydrogel" or "SiHy" interchangeably refers to a hydrogel containing silicone. Silicone hydrogel (SiHy) is typically obtained by copolymerizing a polymerizable composition comprising at least one silicone-containing vinyl monomer or at least one silicone-containing vinyl macromonomer or at least one silicone-containing prepolymer having ethylenically unsaturated groups.
[0027] As used herein, "hydrophilic" describes a material or portion thereof that will associate with water more readily than with lipids.
[0028] The term "room temperature" refers to a temperature of about 22°C to about 26°C.
[0029] The term "soluble" with respect to a compound or material in a solvent means that the compound or material can be dissolved in the solvent at room temperature to give a solution having a concentration of at least about 0.5% by weight.
[0030] The term "insoluble" with respect to a compound or material in a solvent means that the compound or material can be dissolved in the solvent at room temperature (as defined above) to give a solution having a concentration of less than 0.01% by weight.
[0031] "Vinyl monomer" refers to a compound having a single ethylenically unsaturated group, which is soluble in a solvent and which can be polymerized actinically or thermally.
[0032] As used in this application, the term "ethylene crosslinker" refers to a compound having at least two ethylenically unsaturated groups. "Ethylene crosslinker" refers to a subclass of ethylene crosslinkers each having a number average molecular weight of 700 Daltons or less.
[0033] The term "ethylenically unsaturated group" is used herein in a broad sense and is intended to encompass any group containing at least one >C=CH2 group. Exemplary ethylenically unsaturated groups include, but are not limited to, (meth)acryloyl Vinyloxycarbonylamino Where R o is H or C1-C4 alkyl), vinyloxycarbonyloxy Allyl, vinyl, styryl or other C=C containing groups.
[0034] "Acrylic monomer" refers to a vinyl monomer having a single (meth)acryloyl group. Examples of acrylic monomers include (meth)acryloxy (or (meth)acryloyloxy) monomers and (meth)acrylamide monomers.
[0035] "(meth)acryloxy or (meth)acryloyloxy) monomer" means a monomer having a single group of vinyl monomers.
[0036] "(Meth)acrylamide-based monomers" means monomers having a single group (where R o It is a vinyl monomer containing H or C1-C4 alkyl).
[0037] The term "(meth)acrylamide" refers to methacrylamide and / or acrylamide.
[0038] The term "(meth)acrylate" refers to methacrylate and / or acrylate.
[0039] "N-vinyl amide monomer" refers to an amide compound having a vinyl group (-CH=CH2) directly attached to the nitrogen atom of the amide group.
[0040] The term "ene group" refers to a monovalent group of CH2=CH- or CH2=CCH3- that is not covalently attached to an oxygen or nitrogen atom or a carbonyl group.
[0041] "Ethylenic monomer" refers to a vinylic monomer having one and only one olefinic group.
[0042] The "vinyloxycarbonylamino monomer" refers to a vinyl monomer having only one vinyloxycarbonylamino group.
[0043] "Vinylaminocarbonyloxy monomer" refers to a vinylic monomer having a unique vinylaminocarbonyloxy group.
[0044] "Vinylaminocarbonylamino monomer" refers to a vinyl monomer having one and only one vinylaminocarbonylamino group.
[0045] "Hydrophilic vinylic monomer" refers to any vinylic monomer that typically yields a homopolymer that is water soluble or can absorb at least 10% by weight of water.
[0046] "Hydrophobic vinylic monomer" refers to a vinylic monomer that typically produces a homopolymer that is insoluble in water and can absorb less than 10% by weight of water.
[0047] The "acrylic crosslinking agent" refers to a vinyl crosslinking agent having at least two (meth)acryloyl groups.
[0048] The term "acrylic repeating units" refers to repeating units of a polymeric material, each of which is derived from an acrylic monomer or a cross-linking agent that is free radically polymerized to form the polymeric material.
[0049] As used herein, "actinically" with respect to the curing, crosslinking or polymerization of a polymerizable composition, prepolymer or material means curing (e.g., crosslinking and / or polymerization) by actinic irradiation, such as, for example, UV / visible light irradiation, ionizing radiation (e.g., gamma ray or X-ray irradiation), microwave irradiation, etc. Thermal or actinic curing methods are well known to those skilled in the art.
[0050] "Blended vinylic monomers" refers to vinylic monomers that are capable of dissolving both the hydrophilic and hydrophobic polymerizable components of the polymerizable composition to form a solution.
[0051] "Silicone-containing vinylic monomers or crosslinkers" or "siloxane-containing vinylic monomers or crosslinkers" interchangeably refer to vinylic monomers or crosslinkers having at least one -Si-O-Si- moiety, wherein each Si atom carries at least two substituents (organic groups).
[0052] The term "terminal ethylenically unsaturated group" refers to an ethylenically unsaturated group at one of the two ends of the main chain (or backbone) of an organic compound, as known to those skilled in the art. The term "terminal (meth)acryloyl group" refers to a (meth)acryloyl group at one of the two ends of the main chain (or backbone) of an organic compound, as known to those skilled in the art.
[0053] "Polysiloxane segments" or "polydiorganosiloxane segments" refer interchangeably to A polymer chain segment (i.e., a divalent group) wherein SN is an integer of 3 or greater, and R S1 and R S2 Each of which is independently selected from the group consisting of: C1-C 10 Alkyl; phenyl; C1-C4-alkyl substituted phenyl; C1-C4-alkoxy substituted phenyl; phenyl-C1-C6-alkyl; C1-C 10 Fluoroalkyl; C1-C 10 Fluoroether; Aryl; Aryl C1-C 18 Alkyl; -alk-(OC2H4) γ1 -OR o (where alk is a C1-C6 alkylene diradical, R o is H or C1-C4 alkyl and γ1 is an integer from 1 to 10); C2-C 40 An organic group having at least one selected from the group consisting of hydroxyl (-OH), carboxyl (-COOH), amino (-NR N1 R N1 '),-NR N1 -amino bond, -CONR N1 -amide bond, -CONR N1 R N1 'amide, -OCONH-carbamate bond and C1-C4 alkoxy group consisting of a functional group, and a linear hydrophilic polymer chain, wherein R N1 and R N1 'are independently hydrogen or C1-C 15 alkyl.
[0054] "Polydiorganosiloxane vinylic monomer" or "polysiloxane vinylic monomer" interchangeably refers to a compound containing at least one polysiloxane segment and one unique ethylenically unsaturated group.
[0055] "Polydiorganosiloxane vinyl crosslinker" or "polysiloxane vinyl crosslinker" interchangeably refers to a compound comprising at least one polysiloxane segment and at least two ethylenically unsaturated groups.
[0056] "Linear polydiorganosiloxane vinyl crosslinker" or "linear polysiloxane vinyl crosslinker" interchangeably refers to a compound comprising a backbone comprising at least one polysiloxane segment and terminated at each of the two ends of the backbone with an ethylenically unsaturated group.
[0057] "Chain-extended polydiorganosiloxane vinyl crosslinker" or "chain-extended polysiloxane vinyl crosslinker" interchangeably refers to a compound comprising at least two ethylenically unsaturated groups and at least two polysiloxane segments, each pair of which is linked by a divalent group.
[0058] The term "fluid" as used herein indicates a material that is capable of flowing like a liquid.
[0059] As used herein, the term "transparent" with respect to the polymerizable composition means that the polymerizable composition is a transparent solution or liquid mixture having a light transmittance of 85% or more, preferably 90% or more, between 400 and 700 nm.
[0060] "Macromer" or "prepolymer" refers to a compound or polymer containing ethylenically unsaturated groups and having a number average molecular weight >700 Daltons.
[0061] As used herein, the term "polymer" means a material formed by polymerizing or cross-linking one or more monomers, macromers, prepolymers, or combinations thereof.
[0062] As used in this application, the term "molecular weight" of a polymeric material (including monomeric or macromolecular monomeric materials) refers to the number average molecular weight, unless specifically indicated otherwise or unless the test conditions indicate otherwise. The skilled person knows how to determine the molecular weight of a polymer according to known methods, such as GPC (gel permeation chromatography) with one or more of the following: a refractive index detector, a small angle laser light scattering detector, a multi-angle laser light scattering detector, a differential viscometry detector, a UV detector, and an infrared (IR) detector; MALDI-TOF MS (matrix-assisted laser desorption / ionization time-of-flight mass spectrometry); 1 H NMR (proton nuclear magnetic resonance) spectroscopy, etc.
[0063] The term "monovalent group" refers to an organic group obtained by removing a hydrogen atom from an organic compound and forming a bond with one other group in the organic compound. Examples include, but are not limited to, alkyl (by removing a hydrogen atom from an alkane), alkoxy (alkoxyl) (by removing a hydrogen atom from the hydroxyl group of an alkyl alcohol), thiol (thiyl) (by removing a hydrogen atom from the thiol group of an alkylthiol), cycloalkyl (by removing a hydrogen atom from a cycloalkane), cycloheteroalkyl (by removing a hydrogen atom from a cycloheteroalkane), aryl (by removing a hydrogen atom from an aromatic ring of an aromatic hydrocarbon), heteroaryl (by removing a hydrogen atom from any ring atom), amino (by removing a hydrogel atom from an amine), etc.
[0064] The term "divalent group" refers to an organic group obtained by removing two hydrogen atoms from an organic compound and forming two bonds with two other groups in the organic compound. For example, an alkylene (i.e., alkylenyl) divalent group is obtained by removing two hydrogen atoms from an alkane, and a cycloalkylene (i.e., cycloalkylenyl) divalent group is obtained by removing two hydrogen atoms from a ring.
[0065] In the present application, the term "substituted" with respect to an alkyl group or an alkylene group means that the alkyl group or the alkylene group contains at least one substituent, which replaces one hydrogen atom of the alkyl group or the alkylene group and is selected from the group consisting of: hydroxyl (-OH), carboxyl (-COOH), -NH2, mercapto (-SH), C1-C4 alkyl, C1-C4 alkoxy, C1-C4 alkylthio (alkyl sulfide), C1-C4 acylamino, C1-C4 alkylamino, di-C1-C4 alkylamino, and combinations thereof.
[0066] The term "alkyl" refers to a monovalent group obtained by removing a hydrogen atom from a straight or branched chain alkane compound. The alkyl group (group) forms a bond with one other group in an organic compound.
[0067] The terms "alkylene divalent group" or "alkylenediyl" or "alkyldiyl" interchangeably refer to a divalent group obtained by removing one hydrogen atom from an alkyl group. An alkylene divalent group forms two bonds with other groups in an organic compound.
[0068] The term "alkoxy" or "alkoxyl" refers to a monovalent group obtained by removing a hydrogen atom from a hydroxyl group of a straight-chain or branched alkyl alcohol. The alkoxy group (group) forms a bond with one other group in an organic compound.
[0069] As used herein, the term "amino" refers to a primary or secondary amino group having the formula -NHR', wherein R' is hydrogen or C1-C 20 Unsubstituted or substituted, linear or branched alkyl, unless expressly stated otherwise.
[0070] As used in this application, the term "phosphorylcholine" refers to A zwitterionic group, wherein t1 is an integer from 1 to 5, and 1 R. 2 R and 3 R is independently C1-C8 alkyl or C1-C8 hydroxyalkyl.
[0071] As used in this application, the term "carboxyl-containing vinyl monomer" refers to any vinyl monomer having a carboxyl group (-COOH); the term "amino-containing vinyl monomer" refers to any vinyl monomer having an amino group (-NHR', wherein R' is H or a C1-C4 alkyl); the term "epoxy-containing vinyl monomer" refers to any vinyl monomer having a monovalent epoxy group ( wherein each R0' is independently H or C1-C4 alkyl); the term "phosphorylcholine-containing vinyl monomer" refers to any vinyl monomer having a phosphorylcholine group; the term "polyethylene glycol-containing vinyl monomer" refers to any vinyl monomer having Any vinyl monomer containing a polyethylene glycol group, wherein R" is H or a C1-C4 alkyl group; t2 is an integer from 3 to 100.
[0072] As used in this application, the term "non-reactive vinylic monomer" refers to any vinylic monomer that does not contain a carboxyl group, a primary amino group, a secondary amino group, an epoxy group, an isocyanate group, an azlactone group, an aldehyde group, an azetidinium group, or an aziridine group.
[0073] The free radical initiator can be a photoinitiator or a thermal initiator. "Photoinitiator" refers to a chemical that initiates a free radical crosslinking / polymerization reaction by utilizing light. "Thermal initiator" or "thermal free radical initiator" interchangeably refers to a chemical that initiates a free radical crosslinking / polymerization reaction by applying heat.
[0074] The material’s inherent “oxygen permeability” Dk i is the rate at which oxygen passes through a material. As used herein, the term "oxygen permeability (Dk)" with respect to a hydrogel (silicone or non-silicone) or contact lens means the corrected oxygen permeability (Dk c ), which is measured according to the procedure described in ISO 18369-4 at about 34°C-35°C and corrected for the surface resistance to oxygen flux caused by boundary layer effects. Oxygen permeability is conventionally expressed in barrers, where "barrer" is defined as [(cm 3 Oxygen)(cm) / (cm 2 )(s)(mm Hg)]×10 -9 .
[0075] The "oxygen transmission rate" Dk / t of a lens or material is the rate at which oxygen will pass through a particular lens or material having an average thickness t [in mm] over the area being measured. Oxygen transmission rate is conventionally expressed in barrers / mm, where "barrers / mm" is defined as [(cm 3 Oxygen) / (cm 2 )(s)(mm Hg)]×10 -9 .
[0076] The term "modulus" or "elastic modulus" with respect to a contact lens or material means the tensile modulus or Young's modulus which is a measure of the stiffness of a contact lens or material under tension. One skilled in the art is familiar with how to determine the elastic modulus of a SiHy material or contact lens. For example, all commercial contact lenses have a reported elastic modulus value.
[0077] "Coating" in relation to a contact lens means that the contact lens has on its surface a thin layer of material which is different from the bulk material of the contact lens and which is obtained by subjecting the contact lens to a surface treatment.
[0078] As used herein, "surface modification" or "surface treatment" means that the article has been treated in a surface treatment process in which (1) a coating is applied to the surface of the article, (2) a chemical substance is adsorbed onto the surface of the article, (3) the chemical nature of chemical groups on the surface of the article is changed (e.g., electrostatic charge), or (4) the surface characteristics of the article are otherwise modified. Exemplary surface treatment processes include, but are not limited to, surface treatment by energy (e.g., plasma, electrostatic charge, irradiation or other energy sources), chemical treatment, grafting of hydrophilic vinyl monomers or macromers onto the surface of the article, the mold transfer coating process disclosed in U.S. Pat. No. 6,719,929, incorporation of wetting agents into lens formulations for making contact lenses as proposed in U.S. Pat. Nos. 6,367,929 and 6,822,016, enhanced mold transfer coating disclosed in U.S. Pat. No. 7,858,000, and hydrophilic coatings consisting of one or more layers of one or more hydrophilic polymers covalently attached or physically deposited on the surface of the contact lens as disclosed in U.S. Pat. Nos. 8,147,897, 8,409,599, 8,557,334, 8,529,057, and 9,505,184.
[0079] "Post-cure surface treatment" with respect to a lens bulk material or contact lens means a surface treatment process performed after the lens bulk material or contact lens is formed by curing (ie, polymerizing thermally or actinically) a polymerizable composition.
[0080] "Hydrophilic surface" with respect to a silicone hydrogel material or a contact lens means that the silicone hydrogel material or contact lens has a surface hydrophilicity characterized by having an average water contact angle of about 90 degrees or less, preferably about 80 degrees or less, more preferably about 70 degrees or less, more preferably about 60 degrees or less.
[0081] "Average contact angle" refers to the water contact angle (static water contact angle measured by the Sessile Drop method) obtained by averaging the measurements of at least 3 individual contact lenses.
[0082] As used herein, "ophthalmically compatible" refers to materials or surfaces of materials that can be in intimate contact with the ocular environment for extended periods of time without significant damage to the ocular environment and without significant user discomfort.
[0083] The term "ophthalmically safe" with respect to packaging solutions for sterilizing and storing contact lenses means that contact lenses stored in the solution are safe to place directly on the eye without rinsing after autoclaving, and that the solution is safe and sufficiently comfortable for daily contact with the eye through the contact lenses. The ophthalmically safe packaging solution after autoclaving has a tonicity and pH that is compatible with the eye and is substantially free of eye irritant or eye cytotoxic materials in accordance with international ISO standards and U.S. FDA regulations.
[0084] The term "water gradient" with respect to a contact lens means the increase in water content observed from the core to the surface of the contact lens, reaching a maximum water content in a region of the contact lens near and including the surface. It should be understood that the increase in water content from the core to the surface of the contact lens can be continuous and / or stepwise, as long as the water content is highest in the region of the contact lens near and including the surface.
[0085] As used in this application, the term "cross-section" of a contact lens refers to a cross-section of the lens obtained by cutting through the lens with a knife or cutting tool at an angle substantially normal to either the front surface or the back surface of the lens. It is well known to those skilled in the art to cut a contact lens manually (i.e., hand cutting) or with a Cryosta Microtome or with a lathe to obtain a cross-section of a contact lens. The resulting cross-section of the contact lens can be polished by using ion etching or similar techniques.
[0086] As used in this application, the term "equilibrium water content" with respect to a contact lens or polymeric material means the amount of water (expressed as weight percent) present in the contact lens or polymeric material when fully hydrated (equilibrium) in a phosphate-buffered saline solution (approximately 0.79 wt % NaCl) and determined at room temperature.
[0087] As used in this application, the terms "crosslinked coating" or "hydrogel coating" or "hydrogel layer" on a contact lens are used interchangeably to describe a crosslinked polymer material having a three-dimensional network that can hold water when fully hydrated. The three-dimensional network of the crosslinked polymer material can be formed by crosslinking two or more linear or branched polymers.
[0088] As used in this application, the term "lens bulk material" with respect to contact lenses interchangeably means a layer having the 3-dimensional shape of the contact lens and including a central curved plane (which divides the contact lens into two parts, one containing the front surface and the other containing the back surface) and having a variable thickness.
[0089] As used in this application, the term "outer surface hydrogel layer" with respect to a contact lens means the outermost hydrogel layer below the surface of the contact lens, which is composed of an outer front surface hydrogel layer and an outer back surface hydrogel layer and which completely covers the lens body material. The "outer front surface hydrogel layer" with respect to a contact lens means the outermost hydrogel layer below the front surface of the contact lens. The "outer back surface hydrogel layer" with respect to a contact lens means the outermost hydrogel layer below the back surface of the contact lens. It is understood that the front surface is composed of the same material as the outer front surface hydrogel layer, and the back surface is composed of the same material as the outer back surface hydrogel layer.
[0090] As used in this application, the term "transition layer" with respect to a contact lens means a layer of polymeric material located between the inner layer (or bulk lens material) and one of the anterior and posterior outer hydrogel layers.
[0091] Figure 1 A contact lens of the present invention according to a preferred embodiment is schematically shown. According to this preferred embodiment of the present invention, the contact lens 100 has a front surface (or front curve surface or convex surface) 101 and an opposite rear surface (or base curve surface or concave surface) 102, which is placed against the cornea of the eye when worn by the user. The contact lens 100 includes a lens body material 110, an outer front surface hydrogel layer 120 and an outer rear surface hydrogel layer 120. The lens body material 110 has a 3-dimensional shape that is very close to the contact lens 100. The outer front surface hydrogel layer and the outer rear surface hydrogel layer 120 are made of a hydrogel material that is substantially free of silicone (preferably completely free of silicone), and these hydrogel layers have a higher water content relative to the inner layer 110. The front outer hydrogel layer and the rear outer hydrogel layer 120 merge at the peripheral edge 103 of the contact lens 100 and completely cover the inner layer 110.
[0092] The present invention generally relates to a method for preparing a coated contact lens, especially a coated SiHy contact lens, in a cost-effective and time-saving manner. The coated contact lens produced according to the method of the present invention comprises a front surface, an opposite back surface, and a layered structure configuration from the front surface to the back surface, wherein the layered structure configuration comprises an outer front surface hydrogel layer, an inner layer, and an outer back surface hydrogel layer, wherein the inner layer is a lens bulk material, wherein the outer front surface hydrogel layer and the outer back surface hydrogel layer comprise a cross-linked polymer material, the cross-linked polymer material comprises polymer chains derived from a hydrophilic copolymer, the hydrophilic copolymer comprising (a) at least one monomer unit of an epoxy-containing vinyl monomer, (b) at least one primary The invention relates to a method for preparing a hydrophilic copolymer comprising: (a) a hydrophilic copolymer comprising: (i) monomer units of an amino group-containing vinyl monomer containing an amino group or a secondary amino group, (c) monomer units of at least one vinyl monomer containing polyethylene glycol, and (d) monomer units of at least one vinyl monomer containing phosphorylcholine, wherein the sum of the amounts of components (a) and (b) in the at least one hydrophilic copolymer is about 40% or less by mole, wherein the outer front surface hydrogel layer and the outer back surface hydrogel layer are covalently attached to the inner layer through bonds each formed between one carboxylic acid group and one epoxy group, wherein the contact lens has a water break up time (WBUT) of at least 10 seconds.
[0093] The present invention is based in part on the discovery that coated contact lenses having a hydrogel coating thereon can be prepared by autoclaving a contact lens precursor having carboxylic acid groups thereon directly in a lens package containing the contact lens precursor immersed in a lens packaging solution, the lens packaging solution comprising a hydrophilic copolymer containing (a) epoxy-containing monomer units, (b) amino-containing monomer units, (c) phosphorylcholine-containing monomer units, and (d) polyethylene glycol-containing monomer units, wherein the sum of the amounts of components (a) and (b) in the at least one hydrophilic copolymer is about 40% or less by mole. Typically, contact lenses that are hydrated and packaged in the packaging solution must be sterilized. During manufacturing and packaging, sterilization of the hydrated lenses is typically achieved by autoclaving. The autoclaving process involves heating the package of contact lenses under pressure to a temperature of about 118° C. to about 125° C. for at least 30 minutes. It has been discovered that during autoclaving, a hydrogel coating can be formed on a contact lens precursor having carboxylic acid groups thereon, such that the resulting coated contact lens is rendered superior in lens surface hydrophilicity.
[0094] It is believed that the amino and quaternary ammonium groups of the hydrophilic copolymer can enhance the binding of the hydrophilic copolymer on the surface of the contact lens precursor through hydrogen bonding and ionic interactions, while the epoxy groups of the hydrophilic copolymer can react with the carboxylic acid groups on the surface of the contact lens precursor during autoclaving to form covalent linkages to covalently attach the layer of the hydrophilic copolymer to the contact lens precursor. It is also believed that intermolecular and intramolecular reactions can also occur between epoxy and amino groups within the same molecule and between molecules of the hydrophilic copolymer to form a hydrogel coating on the contact lens precursor during autoclaving. The resulting hydrogel coating can provide superior surface hydrophilicity to the resulting coated contact lens due to the pendant hydrophilic polyethylene glycol chains and the pendant hydrophilic zwitterionic phosphorylcholine groups.
[0095] In one aspect, the present invention provides a method for preparing a coated contact lens, the method comprising the following steps: (1) obtaining a contact lens precursor having a concave surface and an opposite convex surface and comprising a lens bulk material and carboxylic acid groups on and / or near the anterior and posterior surfaces; (2) immersing the contact lens precursor in an aqueous solution in a container, wherein the aqueous solution comprises from about 0.01% to about 5.0% (preferably from about 0.05% to about 4.0%, more preferably from about 0.1% to about 3%, even more preferably from about 0.2% to about 2.5%) by weight of at least one hydrophilic copolymer, the hydrophilic copolymer comprising the following monomer units: (a) at least one epoxy-containing vinyl monomer, (b) at least one amino-containing vinyl monomer having primary or secondary amino groups, (c) ) at least one vinyl monomer containing polyethylene glycol, and (d) at least one vinyl monomer containing phosphorylcholine, wherein the sum of the amounts of components (a) and (b) in the at least one hydrophilic copolymer is about 40% or less (preferably about 35% or less, more preferably about 30% or less, even more preferably about 25% or less) by mole; and (3) heating the aqueous solution having a contact lens precursor therein at a temperature of about 100° C. to about 140° C. for at least 30 minutes to form a coated contact lens having a hydrogel coating thereon, wherein the hydrogel coating is covalently attached to the anterior surface and the posterior surface through bonds each formed between one carboxylic acid group and one epoxy group, wherein the hydrogel coating comprises a cross-linked polymer material comprising polymer chains derived from the hydrophilic copolymer.
[0096] In another aspect, the present invention provides a contact lens, preferably a silicone hydrogel contact lens, comprising a front surface, an opposite back surface, and a layered structural configuration from the front surface to the back surface, wherein the layered structural configuration comprises an outer front surface hydrogel layer, an inner layer, and an outer back surface hydrogel layer, wherein the inner layer comprises a lens bulk material and has carboxylic acid groups on and / or near the surface of the inner layer, wherein the outer front surface hydrogel layer and the outer back surface hydrogel layer comprise a cross-linked polymer material, the cross-linked polymer material comprises polymer chains derived from a hydrophilic copolymer, the hydrophilic copolymer comprising the following monomer units: (a) at least one vinyl monomer containing an epoxy group, (b) at least one vinyl monomer containing a primary or secondary amino group, (a) an amino group-containing vinyl monomer, (c) at least one polyethylene glycol-containing vinyl monomer, and (d) at least one phosphorylcholine-containing vinyl monomer, wherein the sum of the amounts of components (a) and (b) in the at least one hydrophilic copolymer is about 40% or less (preferably about 35% or less, more preferably about 30% or less, even more preferably about 25% or less) by mole, wherein the outer front surface hydrogel layer and the back surface hydrogel layer are covalently attached to the inner layer through bonds each formed between one carboxylic acid group and one epoxy group, wherein the contact lens has a water break-up time (WBUT) of at least 10 seconds (preferably at least 12.5 seconds, more preferably at least 15 seconds, even more preferably at least 17.5 seconds).
[0097] According to all aspects of the present invention, the contact lens precursor or inner layer of the present invention can be directly derived from a preformed contact lens. The preformed contact lens can be any contact lens that has not been subjected to any surface treatment after production according to any lens manufacturing process, any contact lens that has been plasma treated or treated with any chemical or physical surface modification, or any commercial contact lens, as long as there is no hydrogel coating on the surface of the preformed contact lens. It is well known to those skilled in the art how to prepare preformed contact lenses. It is well known to those skilled in the art how to prepare preformed contact lenses. For example, the preformed contact lens can be produced in conventional "rotational casting molding" as described, for example, in US 3408429, or produced in a static form by a full cast molding process as described in US Pat. Nos. 4347198; 5508317; 5583463; 5789464; and 5849810, or produced by lathe cutting of polymer material buttons as used in the manufacture of customized contact lenses. In cast molding, a polymerizable composition (ie, lens formulation) is typically dispensed into a mold and cured (ie, polymerized and / or cross-linked) in the mold for making a contact lens.
[0098] Lens molds for preparing contact lenses are well known to those skilled in the art and are used, for example, in cast molding or spin casting. For example, a mold (for cast molding) typically includes at least two mold sections (or parts) or mold halves, namely a first and a second mold half. The first mold half defines a first molding (or optical) surface and the second mold half defines a second molding (or optical) surface. The first mold half and the second mold half are configured to receive each other so that a lens forming cavity is formed between the first molding surface and the second molding surface. The molding surface of the mold half is the cavity forming surface of the mold and is in direct contact with the polymerizable composition.
[0099] Methods of making mold sections for cast-molding contact lenses are generally well known to those skilled in the art. The methods of the present invention are not limited to any particular method of forming the mold. In fact, any method of forming the mold may be used in the present invention. The first and second mold halves may be formed by various techniques such as injection molding or lathing. Examples of suitable methods for forming mold halves are disclosed in U.S. Pat. Nos. 4,444,711; 4,460,534; 5,843,346; and 5,894,002.
[0100] Almost all materials known in the art for making molds can be used to make molds for making contact lenses. For example, polymer materials such as polyethylene, polypropylene, polystyrene, PMMA, COC grade 8007-S10 (a transparent amorphous copolymer of ethylene and norbornene from Ticona GmbH, Frankfurt, Germany and Summit, New Jersey, USA), etc. Other materials that allow UV light transmission may be used, such as quartz glass and sapphire.
[0101] In a preferred embodiment, a reusable mold is used and the lens forming composition is actinically cured under spatial confinement of actinic radiation to form a contact lens. Examples of preferred reusable molds are those disclosed in U.S. Pat. Nos. 6,627,124, 6,800,225, 7,384,590, and 7,387,759. The reusable mold can be made of quartz, glass, sapphire, CaF2, cyclic olefin copolymers (e.g., from Ticona Inc. of Frankfurt, Germany and Summit, New Jersey). COC grade 8007-S10 (a transparent amorphous copolymer of ethylene and norbornene), from Zeon Chemicals LP, Louisville, KY and ), polymethyl methacrylate (PMMA), Delrin from DuPont, and (Polyetherimide), Etc.
[0102] According to the present invention, the polymerizable composition may be introduced (dispensed) into the cavity formed by the mold according to any known method.
[0103] After the polymerizable composition is dispensed into the mold, it is polymerized to produce a contact lens.Crosslinking may be initiated thermally or actinically, preferably by exposing the polymerizable composition in the mold to spatially confined actinic radiation to crosslink the polymerizable components in the polymerizable composition.
[0104] Opening the mold so that the molded article can be removed from the mold can take place in a manner known per se.
[0105] The molded contact lens can be subjected to lens extraction to remove unpolymerized polymerizable components. The extraction solvent can be any solvent known to those skilled in the art. Examples of suitable extraction solvents are those described below.
[0106] In a preferred embodiment, the preformed contact lens is a hard contact lens comprising a hard plastic material as the lens body material. Preferably, the hard plastic material is a cross-linked polymethacrylate. Those skilled in the art are familiar with how to prepare hard plastic materials, including cross-linked polymethyl methacrylate.
[0107] In another preferred embodiment, the preformed contact lens is a rigid gas permeable contact lens comprising a rigid gas permeable material as the bulk material of the lens. It is well known to those skilled in the art how to prepare a rigid gas permeable contact lens.
[0108] In another preferred embodiment, the prefabricated contact lens is a hybrid contact lens comprising a lens body material consisting essentially of a central optical zone and a peripheral zone, wherein the central optical zone is made of a gas permeable lens material and the peripheral zone is made of a silicone hydrogel or conventional hydrogel lens material and extends outwardly from and surrounds the central optical zone.
[0109] In another preferred embodiment, the preformed contact lens is a non-silicone hydrogel contact lens (or so-called conventional hydrogel contact lens) comprising a non-silicone hydrogel material as the bulk material of the lens.
[0110] The preformed non-silicone hydrogel contact lens can be any commercially available non-silicone hydrogel contact lens, or can be produced according to any known method. For example, to produce a preformed non-silicone hydrogel contact lens, a non-silicone hydrogel lens formulation for cast molding or spin casting molding or for preparing a rod used in lathe cutting of a contact lens is typically: (1) a monomer mixture comprising (a) at least one hydrophilic vinyl monomer (e.g., hydroxyethyl methacrylate, glycerol methacrylate, N-vinyl pyrrolidone, or a combination thereof) and (b) at least one component selected from the group consisting of a crosslinker, a hydrophobic vinyl monomer, a lubricant (or so-called internal wetting agent incorporated into the lens formulation), a free radical initiator (photoinitiator or thermal initiator), a UV absorbing vinyl monomer, a high energy violet light ("HEVL") absorbing vinyl monomer, a visibility tinting agent (e.g., reactive dye, polymerizable dye, pigment or mixture thereof), antimicrobial agent (e.g., preferably silver nanoparticles), bioactive agent, and combinations thereof; or (2) an aqueous solution comprising one or more water-soluble prepolymers and at least one component selected from the group consisting of a hydrophilic vinyl monomer, a crosslinking agent, a hydrophobic vinyl monomer, a lubricant (or so-called internal wetting agent incorporated into the lens formulation), a free radical initiator (photoinitiator or thermal initiator), a UV absorbing vinyl monomer, a HEVL absorbing vinyl monomer, a visible tinting agent (e.g., reactive dye, polymerizable dye, pigment or mixture thereof), an antimicrobial agent (e.g., preferably silver nanoparticles), a bioactive agent, and combinations thereof. The resulting preformed hydrogel contact lens can then be subjected to extraction with an extraction solvent to remove unpolymerized components from the resulting lens and subjected to a hydration process, as known to those skilled in the art. It should be understood that the presence of a lubricant in the hydrogel lens formulation can improve the lubricity of the preformed hydrogel contact lens compared to a control preformed hydrogel contact lens obtained from a control hydrogel lens formulation without a lubricant.
[0111] Preferred examples of water-soluble prepolymers include, but are not limited to, water-soluble cross-linkable poly(vinyl alcohol) prepolymers described in US Pat. No. 5,583,163 and US Pat. No. 6,303,687.
[0112] A variety of non-silicone hydrogel lens formulations have been described in numerous patents and patent applications published as of the filing date of this application and have been used to produce commercial non-silicone hydrogel contact lenses. Examples of commercial non-silicone hydrogel contact lenses include, but are not limited to, alfafilcon A, acofilcon A, deltafilcon A, etafilcon A, focofilcon A, helfilcon A, helfilcon B, hilafilcon B, hioxifilcon A, hioxifilcon B, hioxifilcon D, methafilcon A, methafilcon B, nelfilcon A, nesofilcon A, ocufilcon A, ocufilcon B, ocufilcon C, ocufilcon D, omafilcon A, phemfilcon A, polymacon, samfilcon A, telfilcon A, tetrafilcon A, and vifilcon A.
[0113] In a preferred embodiment, the lens bulk material is composed of a non-silicone hydrogel material comprising at least 50% by mole of repeating units of at least one hydroxyl-containing vinyl monomer, preferably selected from the group consisting of hydroxyethyl (meth)acrylate, glycerol (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-amino-2-hydroxypropyl (meth)acrylate, N-2-hydroxyethyl (meth)acrylamide, N-3-hydroxypropyl (meth)acrylamide, N-2-hydroxypropyl (meth)acrylamide, N-2,3-dihydroxypropyl (meth)acrylamide, N-tris (hydroxymethyl)methyl (meth)acrylamide, vinyl alcohol, allyl alcohol, and combinations thereof, more preferably selected from the group consisting of hydroxyethyl (meth)acrylate, glycerol (meth)acrylate, and vinyl alcohol. The mole percentage of the repeating unit can be calculated based on the non-silicone hydrogel lens formulation used to prepare the non-silicone hydrogel contact lens.
[0114] In another preferred embodiment, the preformed contact lens is a silicone hydrogel contact lens comprising a silicone hydrogel material as the bulk lens material.
[0115] The preformed silicone hydrogel contact lens can be any commercially available silicone hydrogel contact lens, or can be produced according to any known method. For example, to produce preformed silicone hydrogel (SiHy) contact lenses, SiHy lens formulations for cast molding or spincast molding or for preparing SiHy rods used in lathe cutting of contact lenses typically include: (1) at least one hydrophilic vinylic monomer (any one or more of those described later in this application), (2) at least one vinylic cross-linking agent, which includes at least one polysiloxane vinylic cross-linking agent (any one or more of those described later in this application) and / or at least one non-silicone vinylic cross-linking agent (any one or more of those described later in this application), (3) at least one siloxane-containing vinylic monomer (any one or more of those described later in this application), (4) a free radical initiator (a photoinitiator or a thermal initiator), and (5) at least one component selected from the group consisting of a hydrophobic non-silicone vinylic monomer (any one or more of those described later in this application), a UV-absorbing vinylic monomer, a UV / HEVL-absorbing vinylic monomer, a polymerizable visibility tint (i.e., a polymerizable dye), and combinations thereof. The resulting preformed SiHy contact lens can then be subjected to extraction with an extraction solvent to remove unpolymerized components from the resulting lens and subjected to a hydration process, as known to those skilled in the art. In addition, the preformed SiHy contact lens can be a colored contact lens (i.e., a SiHy contact lens having at least one colored pattern printed thereon, as is well known to those skilled in the art).
[0116] Any hydrophilic vinyl monomer can be used in the present invention. Examples of preferred hydrophilic vinyl monomers are alkyl (meth) acrylamides (as described later in this application), hydroxyl-containing acrylic monomers (as described below), amino-containing acrylic monomers (as described later in this application), carboxyl-containing acrylic monomers (as described later in this application), N-vinyl amide monomers (as described later in this application), methylene-containing pyrrolidone monomers (i.e., pyrrolidone derivatives each having a methylene group attached to the pyrrolidone ring at the 3-position or 5-position) (as described later in this application), acrylic monomers having C1-C4 alkoxyethoxy groups (as described later in this application), vinyl ether monomers (as described later in this application), allyl ether monomers (as described later in this application), phosphorylcholine-containing vinyl monomers (as described later in this application), N-2-hydroxyethyl vinyl carbamate, N-carboxyvinyl-β-alanine (VINAL), N-carboxyvinyl-α-alanine, and combinations thereof.
[0117] According to the present invention, any non-silicone vinyl crosslinking agent may be used in the present invention. Examples of preferred non-silicone vinyl crosslinking agents are described later in this application.
[0118] According to the present invention, any polysiloxane vinyl crosslinking agent may be used in the present invention. Examples of preferred polysiloxane vinyl crosslinking agents include, but are not limited to, α,ω-(meth)acryloyloxy-terminated polydimethylsiloxanes of different molecular weights; α,ω-(meth)acrylamide-terminated polydimethylsiloxanes of different molecular weights; α,ω-vinyl carbonate-terminated polydimethylsiloxanes of different molecular weights; α,ω-vinyl carbamate-terminated polydimethylsiloxanes of different molecular weights; bis-3-methacryloyloxy-2-hydroxypropyloxypropyl polydimethylsiloxanes of different molecular weights; N,N,N',N'-tetrakis(3-methacryloyloxy-2-hydroxypropyl)-α,ω-bis-3-aminopropyl-polydimethylsiloxanes of different molecular weights; the reaction product of glycidyl methacrylate and amino-functional polydimethylsiloxanes; the reaction product of azlactone-containing vinyl monomer (any of those described above) and hydroxyl-functional polydimethylsiloxanes; selected from US 5,760,100; U.S. Pat. Nos. 4,136,250, 4,153,641, 4,182,822, 4,189,546, 4,259,467, 4,260,725, 4,261,875, 4,343,927, 4,254,248, 4,355,147, 4,276,402, 4,327,203, 4,341,889, 4,486,577, 4,543,398, 4,605,712, 4,661,575, 4,684,538, 4,703,097, 4,833,218, 4,837,289, 4,9545 86, 4954587, 5010141, 5034461, 5070170, 5079319, 5039761, 5346946, 5358995, 5387632, 5416132, 5449729, 5451617, 5486579, 5962548, 5981675, 6039913, 6762264, 7423074, 8163206, 8480227, 8529057, 8835525, 8993651, 9187601, 10081697, 10301451 and 10465047.
[0119] A preferred class of polysiloxane vinyl crosslinkers are di-(meth)acryloyloxy-terminated polysiloxane vinyl crosslinkers, each of which has dimethylsiloxane units and hydrophilized siloxane units (each of which has a methyl substituent and a monovalent C4-C ... 40 Organic group substituents), more preferably polysiloxane vinyl crosslinkers having formula (H), which are described later in this application and can be prepared according to the procedures disclosed in US Pat. No. 10,081,697.
[0120] Another preferred class of polysiloxane vinyl crosslinking agents is the following vinyl crosslinking agents, each of which contains a sole polysiloxane segment and two terminal (meth)acryloyl groups, which can be obtained from commercial suppliers; prepared by reacting glycidyl (meth)acrylate, (meth)acryloyl chloride with di-amino terminated polydimethylsiloxane or di-hydroxy terminated polydimethylsiloxane; prepared by reacting isocyanatoethyl (meth)acrylate with di-hydroxy terminated polydimethylsiloxane; prepared by reacting amino-containing acrylic monomers with di-carboxyl terminated polydimethylsiloxane in the presence of a coupling agent (carbodiimide); prepared by reacting carboxyl-containing acrylic monomers with di-amino terminated polydimethylsiloxane in the presence of a coupling agent (carbodiimide); or prepared by reacting hydroxyl-containing acrylic monomers with dihydroxy terminated polydisiloxane in the presence of a diisocyanate or diepoxy coupling agent.
[0121] Another preferred class of polysiloxane vinyl crosslinkers are chain-extended polysiloxane vinyl crosslinkers, each of which has: at least two polysiloxane segments connected by a linking group between each pair of polysiloxane segments; and two terminal ethylenically unsaturated groups, which can be prepared according to the procedures described in U.S. Pat. Nos. 5,034,461, 5,416,132, 5,449,729, 5,760,100, 7,423,074, 8,529,057, 8,835,525, 8,993,651, 9,187,601, 1,030,1451, and 1,0465,047.
[0122] Any silicone-containing vinyl monomer can be used in the present invention. Examples of preferred silicone-containing vinyl monomers can be silicone-containing (meth)acrylamide monomers, silicone-containing (meth)acryloyloxy monomers, silicone-containing vinyloxycarbonyloxy monomers, silicone-containing vinyloxycarbonylamino monomers, silicone-containing vinylaminocarbonylamino monomers, or silicone-containing vinylaminocarbonyloxy monomers, each of which contains a bis(trialkylsilyloxy)alkylsilyl group, a tris(trialkylsilyloxy)-silyl group, or a polysiloxane chain (having 2 to 30 siloxane units and end-capped with an alkyl group, a hydroxyalkyl group, or a methoxyalkyl group). Such preferred silicone-containing vinyl monomers may be obtained from commercial suppliers, or alternatively prepared according to known procedures, such as those similar to those described in U.S. Pat. Nos. 5,070,215, 6,166,236, 6,867,245, 7,214,809, 8,415,405, 8,475,529, 8,614,261, 8,658,748, 9,097,840, 9,103,965, 9,217,813, 9,315,669, and 9,475,827, or by The method is obtained by reacting a vinyl monomer (having a reactive functional group, such as an acid chloride, anhydride, carboxyl, hydroxyl, amino, epoxy, isocyanate, aziridine, azlactone or aldehyde group) with a siloxane-containing compound (having a reactive group selected from the group consisting of a hydroxyalkyl group, an aminoalkyl group, an alkylaminoalkyl group, a carboxylalkyl group, an isocyanatealkyl group, an epoxyalkyl group and an aziridinealkyl group) in the presence or absence of a coupling agent under coupling reaction conditions well known to those skilled in the art.
[0123] Any thermal polymerization initiator may be used in the present invention. Suitable thermal polymerization initiators are known to the skilled person and include, for example, peroxides, hydroperoxides, azo-bis(alkyl- or cycloalkylnitrile), persulfates, percarbonates, or mixtures thereof. Examples of preferred thermal polymerization initiators include, but are not limited to, benzoyl peroxide, tert-butyl peroxide, tert-amyl peroxybenzoate, 2,2-bis(tert-butylperoxy)butane, 1,1-bis(tert-butylperoxy)cyclohexane, 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane, 2,5-bis(tert-butylperoxy)-2,5-dimethyl-3-hexyne, bis(1-(tert-butylperoxy)-1-methylethyl)benzene, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, di-tert-butyl diperoxyphthalate, tert-butyl hydroperoxide, tert-butyl peracetate, tert-butyl peroxybenzoate, tert-butyl peroxyisopropyl carbonate, acetyl peroxide, lauroyl peroxide, decanoyl peroxide, dicetyl peroxydicarbonate, di(4-tert-butylcyclohexyl) peroxydicarbonate (Perkadox 16S), di(2-ethylhexyl) peroxydicarbonate, tert-butyl peroxypivalate (Lupersol 11); tert-butyl peroxy-2-ethylhexanoate (Trigonox21-C50), 2,4-pentanedione peroxide, dicumyl peroxide, peracetic acid, potassium persulfate, sodium persulfate, ammonium persulfate, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) (VAZO 33), 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride (VAZO44), 2,2'-azobis(2-amidinopropane) dihydrochloride (VAZO 50), 2,2'-azobis(2,4-dimethylvaleronitrile) (VAZO 52), 2,2'-azobis(isobutyronitrile) (VAZO 64 or AIBN), 2,2'-azobis-2-methylbutyronitrile (VAZO 67), 1,1-azobis(1-cyclohexanecarbonitrile) (VAZO 88); 2,2'-azobis(2-cyclopropylpropionitrile), 2,2'-azobis(methyl isobutyrate), 4,4'-azobis(4-cyanovaleric acid), and combinations thereof. Preferably, the thermal initiator is 2,2'-azobis(isobutyronitrile) (AIBN or VAZO 64).
[0124] Suitable photoinitiators are benzoin methyl ether, diethoxyacetophenone, benzoyl-phosphine oxide, 1-hydroxycyclohexyl phenyl ketone and the Darocur and Irgacur types, preferably Darocur and Darocur Germanium-based Norrish type I photoinitiators (e.g., those described in US 7,605,190). Examples of benzoylphosphine initiators include 2,4,6-trimethylbenzoyldiphenylphosphine oxide; bis-(2,6-dichlorobenzoyl)-4-N-propylphenyl-phosphine oxide; and bis-(2,6-dichlorobenzoyl)-4-N-butylphenylphosphine oxide.
[0125] In the present invention, any hydrophobic non-silicone vinyl monomer can be used. Examples of preferred hydrophobic non-silicone vinyl monomers include (meth) acrylic acid C1-C 10 Alkyl esters (e.g., methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, etc.), cyclohexyl (meth)acrylate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl valerate, styrene, chloroprene, vinyl chloride, vinylidene chloride, (meth)acrylonitrile, 1-butene, butadiene, vinyl toluene, vinyl ethyl ether, perfluorohexylethyl-thio-carbonyl-aminoethyl methacrylate, isobornyl (meth)acrylate, trifluoroethyl (meth)acrylate, hexafluoro-isopropyl (meth)acrylate, hexafluorobutyl (meth)acrylate, and combinations thereof.
[0126] Examples of preferred polymerizable dyes include, but are not limited to, 1,4-bis(4-(2-methacryloyloxyethyl)phenylamino)anthraquinone (Reactive Blue 246), 1,4-bis((2-hydroxyethyl)amino)-9,10-anthracenedione-bis(2-acrylate)ester (Reactive Blue 247).
[0127] Preferred examples of UV-absorbing vinyl monomers having formula (1) include, but are not limited to, 2-(2'-hydroxy-5'-vinylphenyl)-2H-benzotriazole, 2-(2'-hydroxy-5'-methacryloxyphenyl)-2H-benzotriazole, 2-(2'-hydroxy-5'-acryloxyphenyl)-2H-benzotriazole, 2-[2'-hydroxy-5'-(2-methacryloxyethyl)phenyl)]-2H-benzotriazole (Norbloc), 2-[2'-hydroxy-5'-(2-acryloxyethyl)-phenyl)]-2H-benzotriazole, 2-(2'-hydroxy-5'-methacryloxypropylphenyl)-2H-benzotriazole, and 2-(2'-hydroxy-5'-acryloxypropylphenyl)-2H-benzotriazole.
[0128] UV-absorbing vinyl monomers containing benzotriazoles can be prepared according to the procedures described in U.S. Pat. Nos. 3,299,173, 4,612,358, 4,716,234, 4,528,311, 1,025,4,567 or can be obtained from commercial suppliers. Examples of preferred UV / HEVL-absorbing vinyl monomers having formula (2) include, but are not limited to: 2-(2'-hydroxy-3'-methacrylamidomethyl-5'-tert-octylphenyl)-2H-benzotriazole, 2-(2'-hydroxy-5'-methacrylamidophenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-5'-methacrylamidophenyl)-5-methoxybenzotriazole, 2-(2'-hydroxy-5'-methacryloxypropyl-3'-tert-butyl-phenyl)-5- Chlorobenzotriazole, 2-hydroxy-5-methoxy-3-(5-(trifluoromethyl)-2H-benzo[d][1,2,3]triazol-2-yl)benzyl methacrylate (WL-1), 2-hydroxy-5-methoxy-3-(5-methoxy-2H-benzo[d][1,2,3]triazol-2-yl)benzyl methacrylate (WL-5), 3-(5-fluoro-2H-benzo[d][1,2,3]triazol-2-yl)-2-hydroxy-5-methoxybenzyl methacrylate (WL-2), 3-(2H-benzo[d][1,2,3]triazol-2-yl)-2-hydroxy-5-methoxybenzyl methacrylate (WL-3), 3-(5-chloro-2H-benzo[d][1,2,3]triazol-2-yl)-2-hydroxy-5-methoxybenzyl methacrylate (WL-4), 2-hydroxy-5-methoxy-3-(5-methyl-2H-benzo[d][1,2,3]triazol-2-yl)benzyl methacrylate (WL-6), 2-hydroxy-5-methyl- 3-(5-(trifluoromethyl)-2H-benzo[d][1,2,3]triazol-2-yl)benzyl ester (WL-7), 4-allyl-2-(5-chloro-2H-benzo[d][1,2,3]triazol-2-yl)-6-methoxyphenol (WL-8), 2-{2'-hydroxy-3'-tert-butyl-5'-[3"-(4"-vinylbenzyloxy)propoxy]phenyl}-5-methoxy-2H-benzotriazole, 2-(5-chloro-2H-benzotriazol-2-yl)-6-(1,1-dimethylethyl)-4-vinyl-phenol (UVAM), 2-{2'-hydroxy-3'-tert-butyl-5'-[3'-methacryloxypropoxy]phenyl}-2H-benzotriazole, 2-{2'-hydroxy-3'-tert-butyl-5'-[3'-methacryloxypropoxy]phenyl}-5-methoxy-2H-benzotriazole (UV13), 2-{2'-hydroxy-3'-tert-butyl-5'-[3'-methacryloxypropoxy]phenyl}-5-chloro-2H-benzotriazole (UV28), 2-[2'-hydroxy-3'-tert-butyl phenyl]-5-trifluoromethyl-2H-benzotriazole (UV23), 2-(2'-hydroxy-5-methylacrylamidephenyl)-5-methoxybenzotriazole (UV6), 2-(3-allyl-2-hydroxy-5-methylphenyl)-2H-benzotriazole (UV9), 2-(2-hydroxy-3-methylallyl-5-methylphenyl)-2H-benzotriazole (UV12), 2-[3'-tert-butyl-2'-hydroxy-5'-(3"-dimethylvinylsilylpropoxy)-2'-hydroxy-phenyl]-5-trifluoromethyl-2H-benzotriazole (UV23), 2-(2'-hydroxy-5-methylacrylamidephenyl)-5-methoxybenzotriazole (UV6), 2-(3-allyl-2-hydroxy-5-methylphenyl)-2H-benzotriazole (UV9), 2-(2-hydroxy-3-methylallyl-5-methylphenyl)-2H-benzotriazole (UV12), 2-(2'-Hydroxy-5'-methacryloylpropyl-3'-tert-butyl-phenyl)-5-methoxy-2H-benzotriazole (UV16), 2-(2'-Hydroxy-5'-acryloylpropyl-3'-tert-butyl-phenyl)-5-methoxy-2H-benzotriazole (UV16A), 2-methacrylate 3-[3-tert-butyl-5-(5-chlorobenzotriazol-2-yl)-4-hydroxyphenyl]-propyl ester (16-100, CAS#96478-15-8), methacrylate 2-(3 -(tert-butyl)-4-hydroxy-5-(5-methoxy-2H-benzo[d][1,2,3]triazol-2-yl)phenoxy)ethyl ester (16-102); 2-(5-chloro-2H-benzotriazol-2-yl)-6-methoxy-4-(2-propen-1-yl)-phenol (CAS#1260141-20-5); 2-[2-hydroxy-5-[3-(methacryloyloxy)propyl]-3-tert-butylphenyl]-5-chloro-2H-benzotriazole; vinyl monomers containing benzotriazole as disclosed in U.S. Patent No. 10254567.
[0129] SiHy contact lens formulations may also contain other necessary components known to those skilled in the art, such as, for example, antimicrobial agents (e.g., preferably silver nanoparticles), bioactive agents, leachable lubricants (e.g., non-polymerizable hydrophilic polymers, etc.), leachable tear stabilizers (e.g., phospholipids, monoglycerides, diglycerides, triglycerides, glycolipids, glyceroglycolipids, sphingolipids, sphingolipids, etc.), and mixtures thereof, as known to those skilled in the art.
[0130] The polymerizable composition (SiHy lens formulation) can be a solvent-free transparent liquid prepared by mixing all polymerizable components and other necessary components, or a solution prepared by dissolving all desired components in any suitable solvent such as a mixture of water and one or more water-miscible organic solvents, an organic solvent, or a mixture of one or more organic solvents, as known to those skilled in the art. The term "solvent" refers to a chemical that cannot participate in a free radical polymerization reaction.
[0131] Solvent-free lenses SiHy lens formulations typically contain at least one blended vinyl monomer as a reactive solvent for dissolving all other polymerizable components of the solvent-free SiHy lens formulation. Examples of preferred blended vinyl monomers are described later in this application. Preferably, methyl methacrylate is used as a blended vinyl monomer in the preparation of solvent-free SiHy lens formulations.
[0132] Any solvent can be used in the present invention. Examples of preferred organic solvents include, but are not limited to, tetrahydrofuran, tripropylene glycol methyl ether, dipropylene glycol methyl ether, ethylene glycol n-butyl ether, ketones (e.g., acetone, methyl ethyl ketone, etc.), diethylene glycol n-butyl ether, diethylene glycol methyl ether, ethylene glycol phenyl ether, propylene glycol methyl ether, propylene glycol methyl ether acetate, dipropylene glycol methyl ether acetate, propylene glycol n-propyl ether, dipropylene glycol n-propyl ether, tripropylene glycol n-butyl ether, propylene glycol n-butyl ether, dipropylene glycol n-butyl ether, tripropylene glycol n-butyl ether, propylene glycol phenyl ether, dipropylene glycol dimethyl ether, polyethylene glycol, polypropylene glycol, ethyl acetate, butyl acetate, amyl acetate , methyl lactate, ethyl lactate, isopropyl lactate, dichloromethane, 2-butanol, 1-propanol, 2-propanol, menthol, cyclohexanol, cyclopentanol and exonorborneol, 2-pentanol, 3-pentanol, 2-hexanol, 3-hexanol, 3-methyl-2-butanol, 2-heptanol, 2-octanol, 2-nonanol, 2-decanol, 3-octanol, norborneol, tert-butyl alcohol, tert-pentanol, 2-methyl-2-pentanol, 2,3-dimethyl-2-butanol, 3-methyl-3-pentanol, 1-methylcyclohexanol, 2-methyl-2-hexanol, 3,7-dimethyl-3-octanol, 1-chloro- 2-Methyl-2-propanol, 2-methyl-2-heptanol, 2-methyl-2-octanol, 2-methyl-2-nonanol, 2-methyl-2-decanol, 3-methyl-3-hexanol, 3-methyl-3-heptanol, 4-methyl-4-heptanol, 3-methyl-3-octanol, 4-methyl-4-octanol, 3-methyl-3-nonanol, 4-methyl-4-nonanol, 3-methyl-3-octanol, 3-ethyl-3-hexanol, 3-methyl-3-heptanol, 4-ethyl-4-heptanol, 4-propyl-4-heptanol, 4-isopropyl-4-heptanol, 2,4-dimethyl-2-pentanol, 1-methylcyclopentanol, 1 -ethylcyclopentanol, 1-ethylcyclopentanol, 3-hydroxy-3-methyl-1-butene, 4-hydroxy-4-methyl-1-cyclopentanol, 2-phenyl-2-propanol, 2-methoxy-2-methyl-2-propanol, 2,3,4-trimethyl-3-pentanol, 3,7-dimethyl-3-octanol, 2-phenyl-2-butanol, 2-methyl-1-phenyl-2-propanol and 3-ethyl-3-pentanol, 1-ethoxy-2-propanol, 1-methyl-2-pyrrolidone, N,N-dimethylpropionamide, dimethylformamide, dimethylacetamide, dimethylpropionamide, N-methylpyrrolidone, and mixtures thereof.
[0133] A variety of SiHy lens formulations have been described in numerous patents and patent applications published as of the filing date of this application and have been used to produce commercial SiHy contact lenses. Examples of commercial SiHy contact lenses include, but are not limited to, asmofilcon A, balafilcon A, comfilcon A, delefilcon A, efrofilcon A, enfilcon A, fanfilcon A, galyfilcon A, lotrafilcon A, lotrafilcon B, narafilcon A, narafilcon B, senofilcon A, senofilcon B, senofilcon C, smafilcon A, somofilcon A, and stenfilcon A.
[0134] SiHy lens formulations (ie, polymerizable compositions) can be cured (polymerized) thermally or photochemically, preferably in a mold for cast-molded contact lenses, as known to those skilled in the art.
[0135] Thermal polymerization is conveniently carried out, for example, at a temperature of 25° C. to 120° C. and preferably 40° C. to 100° C. The reaction time may vary within a wide range, but is conveniently, for example, 1 to 24 hours or preferably 2 to 12 hours. It is advantageous to degas the components and solvents used in the polymerization reaction beforehand and to carry out the copolymerization reaction under an inert atmosphere, for example, under a nitrogen or argon atmosphere.
[0136] The photochemical polymerization can then be triggered by actinic radiation, for example light, in particular UV light or visible light of a suitable wavelength. The spectral requirements can therefore be controlled, if appropriate, by adding suitable photosensitizers.
[0137] According to the present invention, the silicone hydrogel material as the lens bulk material has an oxygen permeability of about 50 (preferably about 60, more preferably about 70, even more preferably about 90 barrers, most preferably at least about 100 barrers) to about 180 barrers. The silicone hydrogel material may also have an equilibrium water content of about 10% (preferably about 20%, more preferably 30%; even more preferably about 40%) to about 80% by weight. The silicone hydrogel material may further have a bulk elastic modulus (i.e., bulk Young's modulus) of about 0.3 MPa to about 1.8 MPa, preferably about 0.4 MPa to about 1.5 MPa, more preferably about 0.4 MPa to about 1.2 MPa. The oxygen permeability, elastic modulus and water content of the silicone hydrogel material of the contact lens of the present invention can be determined by measuring the oxygen permeability, elastic modulus and water content of the preformed contact lens. Those skilled in the art are familiar with how to determine the elastic modulus and equilibrium water content of a silicone hydrogel material or a SiHy contact lens. For example, all commercial SiHy contact lenses have reported values for oxygen permeability, elastic modulus, and water content.
[0138] The preformed contact lenses of the present invention may be obtained according to any method known to those skilled in the art or to be developed.
[0139] According to the present invention, a contact lens precursor is a preformed contact lens which inherently comprises or has been subjected to at least one post-cure surface treatment to have carboxylic acid groups on and / or adjacent to its surface.
[0140] In the case where the preformed contact lens inherently contains carboxylic acid groups on and / or near its surface, the contact lens precursor is composed of a lens bulk material obtained by polymerizing a polymerizable composition (i.e., a non-silicone hydrogel lens formulation or a silicone hydrogel lens formulation) containing a vinyl monomer, which vinyl monomer further contains at least one carboxylic acid group. Examples of carboxyl-containing vinyl monomers are known in the art and can be obtained from commercial sources or prepared according to known procedures. The lens formulation contains from about 0.1% to about 10%, preferably from about 0.25% to about 7%, more preferably from about 0.5% to about 5%, even more preferably from about 0.75% to about 3% by weight of such carboxyl-containing vinyl monomers.
[0141] The preformed contact lens may also be subjected to a surface treatment to have carboxylic acid groups on and / or near its surface. Any suitable surface treatment may be used in the present invention. Examples of surface treatments include, but are not limited to, plasma treatment; chemical treatment; chemical vapor deposition; grafting (covalently attaching) a compound having at least one reactive functional group onto the (modified or unmodified) surface of the article; graft polymerization of carboxyl-containing vinyl monomers onto the (modified or unmodified) surface of the article; layer-by-layer ("LbL") deposition of one or more polyanionic polymers (having carboxylic acid groups) onto the (modified or unmodified) surface of the preformed contact lens (i.e., a method for forming an LbL coating); covalently attaching one or more polyanionic polymers (having carboxylic acid groups) to the (modified or unmodified) surface of the preformed contact lens; or a combination thereof.
[0142] Plasma treatment refers to a process in which a contact lens is exposed to a plasma to chemically modify the surface of the contact lens. The term "plasma" means an ionized gas (e.g., produced by an electrical glow discharge, which may be composed of electrons, ions of either polarity, atoms and molecules of the gas in any higher state, either in the ground state or in any excited form, and photons). The excited species interact with the solid surface of the article placed in the plasma, resulting in chemical and physical modifications of the material surface. In the case where the plasma is generated by subjecting a gas in a vacuum chamber to an electric charge, typically at radio frequency (rf) (or at microwave or other frequencies), it is generally referred to as a "low temperature plasma". In the case where the plasma is generated by an atmospheric discharge (e.g., an arc discharge) and maintained at the surrounding atmospheric pressure, it is a "high temperature plasma" or "atmospheric pressure plasma".
[0143] For a review of plasma treatment and its uses, see R. Hartmann, "Plasma polymerisation: Grundlagen, Technik und Anwendung, Jahrb." Surface Engineering (1993) 49, pp. 283-296, Battelle-Inst. eV, Frankfurt / Germany; H. Yasuda, "Glow Discharge Polymerization", Journal of Polymer Science: Macromolecular Reviews, Vol. 16 (1981), pp. 199-293; H. Yasuda, "Plasma Polymerization", Academic Press, Inc. (1985); Frank Jansen, "Plasma Deposition Processes", in "Plasma Deposited Thin Films", T. Mort and F. Jansen, eds., CRC Press, Boca Raton (1996); O. Auciello et al. (eds.), "Plasma-Surface Interactions and Processing Materials", vol. 16 (1981), pp. 199-293; of Materials]" published by Kluwer Academic Publishers in the NATO ASI series; Series E: Applied Sciences, Vol. 176 (1990), pp. 377-399; and N. Dilsiz and G. Akovali "Plasma Polymerization of Selected Organic Compounds" Polymer, Vol. 37 (1996), pp. 333-341.
[0144] Known low-pressure plasma treatments include plasma deposition, plasma-induced polymerization, plasma grafting, plasma oxidation, etc. Low-pressure plasma treatments have been used in commercial products, such as FocusNIGHT & and AIR (Alcon) and (Bausch & Lomb). Advantages of plasma coating (e.g., Focus NIGHT & The advantages of plasma treatments are its durability, relatively high hydrophilicity / wettability), and low susceptibility to lipid and protein deposition and adsorption. Examples of plasma treatments are those disclosed in U.S. Pat. Nos. 4,143,949; 4,312,575; 5,464,667, 6,881,269; and 7,078,074. It should be understood that preformed contact lenses typically must be dried prior to plasma treatment at low pressure.
[0145] It is well understood by those skilled in the art that a plasma (i.e., an electric glow discharge plasma) is a partially ionized gas consisting of a high concentration of excited atoms, molecules, ions, and radical species, and is produced by subjecting the gas in a vacuum chamber to an electric field, typically at radio frequencies (RF) (or at microwave or other frequencies).
[0146] As an illustrative example of plasma treatment of silicone hydrogel contact lenses at low pressure, one or more preformed silicone hydrogel contact lenses are placed in a reactor chamber between opposing electrodes. The chamber is then sealed and depressurized by a vacuum system. A significant amount of time is required to pump the system to the operating pressure. When the appropriate pressure is reached in the chamber, a process gas is introduced into the interior of the chamber and the electrodes are powered. Depending on the process gas used, the resulting plasma cloud can apply a thin layer of polymer (or polymer coating) to the lens and / or change the chemical composition of the top layer of the lens surface. After an appropriate time, power is stopped to the electrodes and the reactor chamber is returned to atmospheric pressure so that the lens can be removed.
[0147] Low pressure plasma treatment systems are known to those skilled in the art and have been disclosed in patents and articles. For example, Peng Ho and Yasuda described in their paper (Journal of Biomedical Materials Research, Vol. 22, 919-937 (1988)) a batch low pressure plasma treatment system (or rotary plasma system) comprising a bell-shaped vacuum chamber in which opposed aluminum electrodes are disposed and a rotatable aluminum plate is located between the electrodes and driven by an induction motor within the system. Matsuzawa and Winterton disclosed a linear low pressure plasma system in US 6,881,269.
[0148] According to the present invention, a preformed contact lens in a dry state is treated with a low-pressure plasma generated in a plasma gas (i.e., atmosphere), wherein the plasma gas is composed of a mixture of air, N2, O2, CO2, or a C1-C6 hydrocarbon and a secondary gas selected from the group consisting of air, N2, O2, CO2, and a combination thereof (preferably a mixture of CO2 or a C1-C4 hydrocarbon and a secondary gas selected from the group consisting of air, CO2, N2, and a combination thereof, more preferably a mixture of CO2 or methane and a secondary gas selected from the group consisting of air, CO2, N2, and a combination thereof, and even more preferably a mixture of CO2 or methane and CO2).
[0149] Preferably, the atmospheric pressure plasma surface treatment disclosed in US Patent No. 9156213 is used in the present invention. For the atmospheric pressure plasma surface treatment, the contact lens can be in a fully hydrated state.
[0150] A person skilled in the art is familiar with how to graft (covalently attach) compounds having at least one carboxylic acid group onto the surface of a contact lens according to known coupling reactions.
[0151] As used herein, "LbL coating" refers to a coating that is not covalently attached to the polymer matrix of the contact lens and is obtained by depositing one or more polymer materials on the lens layer by layer ("LbL"). The LbL coating may consist of one or more layers. The LbL coating on the contact lens may be obtained according to the methods described in U.S. Pat. Nos. 6451871, 6719929, 6793973, 6811805, 6896926, 8044112, 8158192, and 8147897. Preferably, the LbL coating comprises at least one layer of one or more polyanionic polymers each comprising a carboxylic acid group. The polyanionic polymer is preferably a polyanionic polymer selected from the group consisting of polyacrylic acid, polymethacrylic acid, polyethylacrylic acid, poly(acrylic acid-co-methacrylic acid), poly(acrylic acid-co-ethylacrylic acid), poly(methacrylic acid-co-ethylacrylic acid), and mixtures thereof, more preferably a polyanionic polymer of polyacrylic acid, polymethacrylic acid, poly(acrylic acid-co-methacrylic acid), or mixtures thereof.
[0152] The LbL coating of the polyanionic polymer having carboxylic acid groups can be formed on the contact lens by contacting the contact lens with a polymer solution. Contacting the contact lens with the coating solution of the polymer can occur by immersing the contact lens in the coating solution or by spraying the contact lens with the coating solution. One contact method involves immersing the contact lens alone in a bath of the coating solution for a period of time or alternatively immersing the contact lens in a series of baths of the coating solution in sequence, each bath lasting a fixed shorter period of time. Another contact method involves spraying the coating solution alone. However, many alternatives involving various combinations of spray-and immersion steps can be designed by a person of ordinary skill in the art. The contact time of the contact lens with the coating solution of the reactive polymer can last up to about 10 minutes, preferably about 5 to about 360 seconds, more preferably about 5 to about 250 seconds, and even more preferably about 5 to about 200 seconds.
[0153] The polyanionic polymer solution for forming a coating on a contact lens can be prepared by dissolving one or more polymers in water, a mixture of water and a water-miscible organic solvent, an organic solvent, or a mixture of one or more organic solvents. Preferably, the polymer is dissolved in a mixture of water and one or more organic solvents, an organic solvent, or a mixture of one or more organic solvents. It is believed that a solvent system containing at least one organic solvent can swell the contact lens so that a portion of the polyanionic polymer can penetrate into the contact lens and increase the durability of the coating. Examples of organic solvents are described above. The pH of the polyanionic polymer solution is preferably about 1.5 to about 4.0 to form a relatively thick and stable LbL coating. The temperature of the coating solution is preferably about 20° C. to about 70° C.
[0154] Those skilled in the art know how to covalently attach one or more polymers having carboxylic acid groups to the surface of a contact lens. Exemplary methods for covalently attaching one or more hydrophilic polymers to a medical device are disclosed in U.S. Pat. Nos. 5,599,576, 5,766,158, 6,087,415, 6,096,726, 6,340,465, 6,440,571, 6,500,481, 6,534,559, 6,623,747, 6,683,062, 6,838,491, 6,866,936, 6,923,978, and 8,529,057 and U.S. Patent Application Publication Nos. 2009-0145086A1, 2009-0145091A1, 2008-0142038A1, and 2007-0122540A1.
[0155] Graft polymerization of a variety of vinyl monomers having at least one carboxylic acid group in the presence or absence of a vinyl crosslinking agent to form a hydrophilic polymer coating is described in many patents, such as U.S. Pat. Nos. 6099122, 6436481, 6440571, 6447920, 6465056, 6521352, 6586038, 6730366, 6734321, 6835410 and 6878399 and JP 2001075060. For example, a preformed contact lens in a dry state is first subjected to a plasma treatment in a plasma atmosphere of a compound having at least one reactive carboxylic acid group to form a plasma coating having carboxylic acid groups. The plasma treated contact lens is reacted with a compound having a free radical initiator moiety (e.g., a thermal initiator or a photoinitiator) or preferably a living polymerization initiator moiety (e.g., an atom transfer radical polymerization (ATRP) initiator or a reversible addition fragmentation chain transfer polymerization (RAFT) initiator) and a functional group co-reactive with the functional group of the plasma coating on the contact lens in the presence or absence of a coupling agent under coupling reaction conditions known to those skilled in the art. The resulting contact lens having the free radical initiator moiety thereon is immersed in a solution of one or more vinyl monomers having at least one carboxylic acid group and subjected to conditions that initiate free radical polymerization of those vinyl monomers, thereby forming a layer of graft-from polymer comprising carboxylic acid groups.
[0156] In a preferred embodiment, the contact lens precursor comprises a lens bulk material and a layer of at least one polymer material having carboxylic acid groups thereon. It should be understood that the layer of at least one polymer material having carboxylic acid groups may be covalently bonded directly to the polymer matrix of the lens bulk material or non-covalently associated with the lens bulk material. Preferably, the at least one polymer material having carboxylic acid groups comprises polyacrylic acid, polymethacrylic acid, polyethylacrylic acid, poly(acrylic acid-co-methacrylic acid), poly(acrylic acid-co-ethylacrylic acid), poly(methacrylic acid-co-ethylacrylic acid), or a mixture thereof.
[0157] According to the present invention, the at least one hydrophilic copolymer comprises (a) at least one preferably having the formula The monomer units of epoxy-containing vinyl monomers, (b) at least one preferably having the formula (c) at least one monomer unit of an amino-containing acrylic monomer preferably having the formula The monomer units of the polyethylene glycol-containing acrylic monomer, and (d) at least one preferably having the formula The monomer unit of the acrylic monomer containing phosphorylcholine, wherein: each R0 is independently H or CH3; each R0' is independently H or C1-C4 alkyl; B1, B2 and B3 are independently O or NR'; R' is H or C1-C4 alkyl; D1, D2 and D3 are independently C1-C 12 Alkylene divalent group; D0 is C1-C 12 An alkylene divalent group or a divalent group of -D4-O-D5-B4-CH2-; B4 is -O- or D4 is C1-C 12 Alkylene divalent group; D5 is a C2-C6 alkylene divalent group or D6 and D7 are independently C2-C6 alkylene divalent groups; d1 is 0, 1 or 2; PEG is A polyethylene glycol group, wherein R" is H or a C1-C4 alkyl group; t2 is an integer from 3 to 100; PC is A zwitterionic group, wherein t1 is an integer from 1 to 5, and 1 R. 2 R and 3 R is independently C1-C8 alkyl or C1-C8 hydroxyalkyl.
[0158] In a preferred embodiment, the at least one hydrophilic copolymer is a statistical copolymer having formula (I),
[0159]
[0160] wherein T' and T" are independently H or a terminal group; each R0 is independently H or CH3; each R0' is independently H or a C1-C4 alkyl group; B1, B2 and B3 are independently O or NR'; R' is H or a C1-C4 alkyl group; D1, D2 and D3 are independently C1-C 12 Alkylene divalent group; D0 is C1-C 12 An alkylene divalent group or a divalent group of -D4-O-D5-B4-CH2-; B4 is -O- or D4 is C1-C 12 Alkylene divalent group; D5 is a C2-C6 alkylene divalent group or D6 and D7 are independently C2-C6 alkylene divalent groups; d1 is 0, 1 or 2; PEG is A polyethylene glycol group, wherein R" is H or a C1-C4 alkyl group; t2 is an integer from 3 to 100; PC is A zwitterionic group, wherein t1 is an integer from 1 to 5, and 1 R. 2 R and3 R is independently C1-C8 alkyl or C1-C8 hydroxyalkyl; a, b, c, and d are independently integers from 5 to 100, wherein (a+c) / (a+b+c+d)≤0.40 (preferably ≤0.35, more preferably ≤0.30, even more preferably ≤0.25). Preferably, a / c is 10 to 0.1 (preferably 5 to 0.2, more preferably 2.5 to 0.4, even more preferably 2 to 0.5).
[0161] Any epoxy-containing vinyl monomer can be used in the present invention. Examples of epoxy-containing vinyl monomers include, but are not limited to, 3,4-epoxy-1-butene, 1,2-epoxy-5-hexene, 2-methyl-2-vinyl oxirane, glycidyl vinyl ether, glycidyl vinyloxyethyl ether, 2-(vinyloxymethyl)-3-methyloxirane, 2-(1-vinyloxyprop-2-yloxymethyl)oxirane, 2-[2-[2-(vinyloxy)ethoxy]ethoxymethyl]oxirane, 2-[2-[2-[2-(vinyloxy)ethoxy]ethoxy]ethoxymethyl]oxirane, 2-[2-[2-[2-(vinyloxy)ethoxy]ethoxy]ethoxymethyl]oxirane, 2-[2-[2-[2-(vinyloxy)ethoxy]ethoxy]ethoxymethyl]oxirane, 2-(3-vinyloxypropoxy-methyl)oxirane, allyl glycidyl ether, 2-[2-(allyloxy)ethoxymethyl]oxirane, [2-[2-(allyloxy)ethoxy]-ethyl]glycidyl ether, 2-[2-[2-(2-prop-2-enyloxyethoxy)ethoxy]ethoxymethyl]oxirane, 2-[3-(2-prop-2-enyloxyethoxy)propoxymethyl]oxirane, 2-(3-prop-2-enyloxypropoxymethyl)oxirane, 2-(but-3-en-2-yloxymethyl)oxirane, 2-methyl-3-(prop-2-enyloxymethyl)oxirane, 2-(1-prop-2-enyloxyethyl)oxirane, 2-[2-[2-(2-prop-2-enyloxyethoxy)ethoxy]ethoxy]ethoxymethyl]oxirane, and preferably an epoxy-containing acrylic monomer.
[0162] Examples of preferred epoxy-containing acrylic monomers include, but are not limited to, glycidyl (meth)acrylate, 2-methylglycidyl (meth)acrylate, 2-[2-(oxiran-2-ylmethoxy)ethoxy]ethyl (meth)acrylate, (3-methyloxiran-2-yl)methyl (meth)acrylate, 2-[2-(oxiran-2-ylmethoxy)propoxy]-propyl (meth)acrylate, 2-[2-(oxiran-2-ylmethoxy)propoxy]ethyl (meth)acrylate, 2-[2-(oxiran-2-ylmethoxy)ethoxy]propyl (meth)acrylate, 2-[2-(oxiran-2-ylmethoxy)propoxy]ethyl (meth)acrylate, 1-(2-methyloxiran-2-yl)ethyl (meth)acrylate, (2,3-dimethyloxiran-2-yl)methyl (meth)acrylate, (3-ethyloxiran-2-yl)methyl (meth)acrylate, 3-(oxiran-2-ylmethoxy)butyl (meth)acrylate, 2-(oxiran-2-ylmethoxy)propyl (meth)acrylate, 1-(oxiran-2-yl)propyl (meth)acrylate, (3,3-dimethyloxiran-2-yl)methyl (meth)acrylate, 3-(oxiran-2-ylmethoxy)propyl (meth)acrylate, [3-(oxiran-2-ylmethoxy)-3-oxopropyl] (meth)acrylate.
[0163] Any amino-containing vinyl monomer can be used in the present invention. Examples of amino-containing vinyl monomers include, but are not limited to, vinylamine, allylamine, N-allylmethylamine, N-allyl-N-ethylamine, 3-buteneamine, 3-(vinyloxy)propylamine, 3-vinyloxy-2-methylprop-1-amine, 1-vinyloxyprop-1-amine, 1-vinyloxy-2-methylprop-1-amine, 3-vinyloxy-2,2-dimethylprop-1-amine, 1-vinyloxypropane-1,3-diamine, [2-(vinyloxy)ethyl]-amine, 3-(prop-2-en-1-yloxy)prop-1-amine, 1-prop-2-enyloxyprop-1-amine. 2-amine, 2-prop-2-enyloxyethylamine, 2-methyl-3-prop-2-enyloxyprop-1-amine, 2-(2-prop-2-enyloxyethoxy)-ethylamine, 2-[2-(2-prop-2-enyloxyethoxy)ethoxy]ethylamine, 2-[2-[2-(2-prop-2-enyloxyethoxy)-ethoxy]ethoxy]ethylamine, 2-[2-[2-(2-prop-2-enyloxyethoxy)ethoxy]ethoxy]ethylamine, 3-methoxy-2-prop-2-enyloxyprop-1-amine, and preferably an amino group-containing acrylic monomer.
[0164] Examples of preferred amino-containing acrylic monomers include, but are not limited to, N-2-aminoethyl(meth)acrylamide, N-2-methylaminoethyl(meth)acrylamide, N-2-ethylaminoethyl(meth)acrylamide, N-2-dimethylaminoethyl(meth)acrylamide, N-3-aminopropyl(meth)acrylamide, N-3-methylaminopropyl(meth)acrylamide, N-3-dimethylaminopropyl(meth)acrylamide, 2-aminoethyl(meth)acrylate, 2-methylaminoethyl(meth)acrylate, 2-ethylaminoethyl(meth)acrylate, 3-aminopropyl(meth)acrylate, 3-methylaminopropyl(meth)acrylate, 3-ethylaminopropyl(meth)acrylate, 3-amino-2-hydroxypropyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate trimethylammonium hydrochloride, and dimethylaminoethyl(meth)acrylate.
[0165] Any polyethylene glycol-containing vinyl monomer can be used in the present invention. Examples of polyethylene glycol-containing vinyl monomers include, but are not limited to, tri(ethylene glycol) monovinyl ether, tetra(ethylene glycol) monovinyl ether, poly(ethylene glycol) monovinyl ether, tri(ethylene glycol) methyl vinyl ether, tetra(ethylene glycol) methyl vinyl ether, poly(ethylene glycol) methyl vinyl ether, tri(ethylene glycol) monoallyl ether, tetra(ethylene glycol) monoallyl ether, poly(ethylene glycol) monoallyl ether, tri(ethylene glycol) methylallyl ether, tetra(ethylene glycol) methylallyl ether, poly(ethylene glycol) methylallyl ether, and preferably acrylic monomers containing polyethylene glycol.
[0166] Examples of preferred polyethylene glycol-containing acrylic monomers include, but are not limited to, tri(ethylene glycol) methyl ether (meth)acrylate, tetra(ethylene glycol) methyl ether (meth)acrylate, C1-C4-alkoxypoly(ethylene glycol) (meth)acrylate having a number average molecular weight of up to 1500, methoxy-poly(ethylene glycol) ethyl (meth)acrylamide having a number average molecular weight of up to 1500, tri(ethylene glycol) (meth)acrylate, tetra(ethylene glycol) (meth)acrylate, poly(ethylene glycol) (meth)acrylate having a number average molecular weight of up to 1500, poly(ethylene glycol) ethyl (meth)acrylamide having a number average molecular weight of up to 1500.
[0167] Any vinyl monomer containing phosphorylcholine can be used in the present invention. Examples of vinyl monomers containing phosphorylcholine include, but are not limited to, 2-(vinyloxy)ethyl 2'-(trimethylammonium)ethyl phosphate, 2-(allyloxy)ethyl 2'-(trimethylammonium)ethyl phosphate, 2-(vinyloxycarbonyl)ethyl 2'-(trimethylammonium)ethyl phosphate, 2-(allyloxycarbonyl)ethyl 2'-(trimethylammonium)ethyl phosphate, 2-(allyloxycarbonylamino)ethyl 2'-(trimethylammonium)ethyl phosphate, 2-(butyleneoxy)ethyl 2'-(trimethylammonium)ethyl phosphate, and preferably an acrylic monomer containing phosphorylcholine.
[0168] Examples of preferred phosphorylcholine-containing acrylic monomers include, but are not limited to, (meth)acryloyloxyethyl phosphorylcholine, (meth)acryloyloxypropyl phosphorylcholine, 4-((meth)acryloyloxy)butyl 2'-(trimethylammonio)ethyl phosphate, 2-[(meth)acryloylamino]ethyl 2'-(trimethylammonio)ethyl phosphate, 3-[(meth)acryloylamino]propyl 2'-(trimethylammonio)-ethyl phosphate, 4-[(meth)acryloylamino]butyl 2'-(trimethylammonio)ethyl phosphate, 5-((meth)acryloyloxy)pentyl 2'-(trimethylammonio)ethyl phosphate, 6-((meth)acryloyloxy)hexyl phosphate 2'-(trimethylammonio)-ethyl phosphate, 2-((meth)acryloyloxy)ethyl phosphate 2'-(triethylammonio)-ethyl phosphate, 2-((meth)acryloyloxy)ethyl phosphate 2'-(tripropylammonio)ethyl phosphate, 2-((meth)acryloyloxy)ethyl phosphate 2'-(tributylammonio)ethyl phosphate, 2-((meth)acryloyloxy)propyl phosphate 2'-(trimethylammonio)-ethyl phosphate, 2-((meth)acryloyloxy)butyl phosphate 2'-(trimethylammonio)-ethyl phosphate, 2-((meth)acryloyloxy)pentyl phosphate 2'-(trimethylammonio)ethyl phosphate, 2-((meth)acryloyloxy)hexyl phosphate 2'-(trimethylammonio)ethyl phosphate.
[0169] The hydrophilic copolymers of the present invention can be obtained by polymerizing a polymerizable composition comprising all required vinylic monomers, a free radical initiator and optionally a chain transfer agent (ie, a thiol-containing compound) according to any procedure known to those skilled in the art.
[0170] According to the present invention, a contact lens precursor having carboxylic acid groups thereon (i.e., a contact lens precursor) is heated in an aqueous solution containing a hydrophilic copolymer of the present invention at a temperature of about 50° C. to about 140° C. for a period of time to crosslink the hydrophilic copolymer of the present invention and simultaneously covalently attach the crosslinked hydrophilic copolymer to a preformed contact lens so as to form a hydrogel coating on the surface of the preformed contact lens.
[0171] Preferably, the heating step is performed by autoclaving the contact lens precursor having carboxylic acid groups thereon (i.e., contact lens precursor) immersed in an aqueous solution, which is a packaging solution in a sealed lens package (i.e., a buffered aqueous solution having a pH of 6.7 to 7.6), at a temperature of about 115° C. to about 125° C. for about 20-90 minutes. It is believed that during autoclaving, a small amount of epoxide (epoxy) groups that do not participate in the cross-linking reaction can be hydrolyzed into 2,3-dihydroxypropyl (HO-CH2-CH(OH)-CH2-) groups, and the hydrophilic copolymer (if applicable) present in the lens packaging solution can be converted into a non-reactive polymer wetting agent that can improve the insertion comfort of the lens. Therefore, the packaging solution is ophthalmologically safe after autoclaving.
[0172] Lens packages (or containers) are well known to those skilled in the art for autoclaving and storing contact lenses. Any lens package can be used in the present invention. Preferably, the lens package is a blister package comprising a base and a cover, wherein the cover is removably sealed to the base, wherein the base comprises a cavity for receiving a sterile packaging solution and a contact lens.
[0173] In another preferred embodiment, the aqueous solution is a packaging solution for storing contact lenses individually in sealed and sterilized lens packages, as is well known to those skilled in the art. According to the present invention, the packaging solution may contain one or more other ingredients known to those skilled in the art. Examples of other ingredients include, but are not limited to, one or more buffers for maintaining the pH of the packaging solution in the range of about 6.8 to about 7.5, preferably about 6.8 to about 7.4, more preferably about 6.9 to about 7.3), surfactants, antibacterial agents, preservatives, and lubricants (e.g., cellulose derivatives, polyvinyl alcohol, polyvinyl pyrrolidone).
[0174] Physiologically compatible buffers have been widely used in contact lens packaging solutions and contact lens care compositions. Examples of such buffers include, but are not limited to, boric acid, borates (e.g., sodium borate, potassium borate), citric acid, citrates (e.g., monopotassium citrate, monosodium citrate; dipotassium citrate; disodium citrate; tripotassium citrate), phosphates (e.g., NaH2PO4, KH2PO4, Na2HPO4, K2HPO4, Na3HPO4, K3HPO4), TRIS (i.e., 2-amino-2-hydroxymethyl-1,3-propanediol), Bis-Tris [i.e., bis-(2-hydroxy-ethyl)-imino-tris-(hydroxymethyl)-methane], Bis-Tris propane [i.e., 1,3-bis(tris(hydroxymethyl)methylamino)propane], bis-aminopolyols, triethanolamine, ACES [i.e., N-( 2-hydroxyethyl)-2-aminoethanesulfonic acid], BES [i.e., N,N-bis(2-hydroxyethyl)-2-aminoethanesulfonic acid], HEPES [i.e., 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid], MES [i.e., 2-(N-morpholino)ethanesulfonic acid], MOPS [i.e., 3-[N-morpholino]-propanesulfonic acid], PIPES [i.e., piperazine-N,N'-bis(2-ethanesulfonic acid], TES {i.e., N-[tris(hydroxymethyl)methyl]-2-aminoethanesulfonic acid}, salts thereof, or mixtures thereof. The total concentration of all buffers present in the aqueous solution is about 10 mM to 100 mM (preferably about 10 mM to 90 mM, more preferably about 10 mM to about 80 mM, even more preferably about 10 mM to 70 mM).
[0175] In a preferred embodiment, the aqueous solution further comprises one or more tonicity regulators, which independently of one another can be ionic or nonionic. Suitable eye-acceptable tonicity regulators include, but are not limited to, sodium chloride, potassium chloride, glycerol, propylene glycol, polyols, mannitol, sorbitol, xylitol, and mixtures thereof. Preferably, nonionic tonicity regulators are used to adjust the osmotic pressure molar concentration of the aqueous solution to a value of about 200 to about 450mOsm / Kg (preferably about 230 to about 400mOsm / Kg, more preferably about 260 to about 350mOsm / Kg).
[0176] The lenses are packaged in individual packages, sealed, and sterilized (eg, by autoclaving under pressure at about 120° C. or higher for at least 30 minutes) prior to distribution to users. One skilled in the art will well understand how to seal and sterilize lens packages.
[0177] The lamellar structural configuration of the contact lenses of the present invention can be determined by analyzing cross-sections of contact lenses in a fully hydrated state (i.e., directly in water or buffered saline) using atomic force microscopy (AFM), alone or in combination with differential staining of the hydrogel coating or bulk lens material, environmental scanning electron microscopy, confocal fluorescence microscopy, or any other known technique, as known to those skilled in the art.
[0178] According to the present invention, the contact lenses of the present invention have at least one property selected from the group consisting of: an equilibrium water content of about 15% to about 70% by weight (preferably about 20% to about 65%, more preferably about 20% to about 60%, even more preferably about 25% to about 55%), an elastic modulus of about 0.2 MPa to about 2.0 MPa (preferably about 0.25 MPa to about 1.5 MPa, more preferably about 0.3 MPa to about 1.2 MPa, even more preferably about 0.35 MPa to about 1.0 MPa), an oxygen permeability of at least 40 barr / mm (preferably at least 60 barr / mm, more preferably at least 80 barr / mm, even more preferably at least 100 barr / mm), and an average water contact angle of less than 90 degrees (preferably less than 80 degrees, more preferably less than 70 degrees, even more preferably less than 60 degrees).
[0179] Although various embodiments of the present invention have been described using specific terms, devices, and methods, such descriptions are for illustrative purposes only. The words used are descriptive rather than restrictive. As should be apparent to those skilled in the art, many variations and modifications of the present invention may be made by those skilled in the art without departing from the spirit and scope of the novel concepts disclosed herein. In addition, it should be understood that various aspects of the various embodiments of the present invention may be interchangeable in whole or in part or may be combined and / or used together in any manner, as illustrated below:
[0180] 1. A method for preparing a coated contact lens, the method comprising the steps of:
[0181] (1) obtaining a contact lens precursor having a concave surface and an opposite convex surface and comprising a lens bulk material and carboxylic acid groups on and / or near the anterior and posterior surfaces;
[0182] (2) immersing a contact lens precursor in an aqueous solution in a container, wherein the aqueous solution comprises from about 0.01% to about 5.0% by weight of at least one hydrophilic copolymer comprising monomer units of: (a) at least one vinyl monomer containing an epoxy group, (b) at least one vinyl monomer containing an amino group having a primary or secondary amino group, (c) at least one vinyl monomer containing polyethylene glycol, and (d) at least one vinyl monomer containing phosphorylcholine, wherein the sum of the amounts of components (a) and (b) in the at least one hydrophilic copolymer is about 40% or less by mole; and
[0183] (3) heating the aqueous solution having the contact lens precursor therein at a temperature of about 100° C. to about 140° C. for at least 30 minutes to form a coated contact lens having a hydrogel coating thereon, wherein the hydrogel coating is covalently attached to the anterior surface and the posterior surface through bonds each formed between a carboxylic acid group and an epoxy group, wherein the hydrogel coating comprises a cross-linked polymer material comprising polymer chains derived from the hydrophilic copolymer,
[0184] Wherein the contact lens has a water break up time (WBUT) of at least 10 seconds.
[0185] 2. The method of embodiment 1, wherein the contact lens precursor is comprised of a lens bulk material having carboxylic acid groups on and / or near the surface of the lens bulk material.
[0186] 3. The method of embodiment 2, wherein the lens bulk material is obtained by polymerizing a polymerizable composition comprising from about 0.1% to about 10% by weight of a vinyl monomer, the vinyl monomer further comprising at least one carboxylic acid group.
[0187] 4. The method of embodiment 2, wherein the lens bulk material has been subjected to at least one post-curing surface treatment to have carboxylic acid groups on and / or near the surface of the lens bulk material.
[0188] 5. The method of any one of embodiments 1 to 4, wherein the contact lens precursor comprises a lens bulk material and a layer of at least one polymer material having carboxylic acid groups thereon.
[0189] 6. A method as described in Example 5, wherein the at least one polymer material having a carboxylic acid group comprises polyacrylic acid, polymethacrylic acid, polyethylacrylic acid, poly(acrylic acid-co-methacrylic acid), poly(acrylic acid-co-ethylacrylic acid), poly(methacrylic acid-co-ethylacrylic acid), or a mixture thereof.
[0190] 7. A method as described in any one of Examples 1 to 6, wherein the method includes the following steps before step (2): contacting the contact lens precursor with a coating solution comprising at least one reactive polymer having carboxylic acid side groups to form a reactive substrate coating comprising the at least one reactive polymer.
[0191] 8. The method of embodiment 7, wherein the at least one reactive polymer comprises a homopolymer or copolymer of acrylic acid or a C1-C3 alkyl acrylic acid.
[0192] 9. The method of embodiment 8, wherein the homopolymer or copolymer of acrylic acid or C1-C3 alkyl acrylic acid is polyacrylic acid, polymethacrylic acid, polyethylacrylic acid, polypropylacrylic acid, poly(acrylic acid-co-methacrylic acid), poly[(meth)acrylic acid-co-ethylacrylic acid], poly[(meth)acrylic acid-co-propylacrylic acid], poly[(meth)acrylic acid-co-acrylamide], poly[(meth)acrylic acid-co-vinylpyrrolidone], poly[ethylacrylic acid-co-acrylamide], poly[ethylacrylic acid-co-vinylpyrrolidone], poly[propylacrylic acid-co-acrylamide], poly[propylacrylic acid-co-vinylpyrrolidone], poly[(meth)acrylic acid-co-vinyl acetate], poly[ethylacrylic acid-co-vinyl acetate], poly[propylacrylic acid-co-vinyl acetate], or a combination thereof.
[0193] 10. The method of any one of embodiments 7 to 9, wherein the coating solution has a pH of about 1.5 to about 5.5.
[0194] 11. The method of any one of embodiments 7 to 10, wherein the coating solution is prepared by dissolving the at least one reactive polymer in water, a mixture of water and one or more organic solvents, an organic solvent, or a mixture of one or more organic solvents and optionally by adding an inorganic acid or an organic acid to adjust the pH of the coating solution.
[0195] 12. The method of any one of embodiments 1 to 11, wherein the aqueous solution comprises from about 0.05% to about 4.0% by weight of the at least one hydrophilic copolymer.
[0196] 13. The method of any one of embodiments 1 to 11, wherein the aqueous solution comprises from about 0.1% to about 3% by weight of the at least one hydrophilic copolymer.
[0197] 14. The method of any one of embodiments 1 to 11, wherein the aqueous solution comprises from about 0.2% to about 2.5% by weight of the at least one hydrophilic copolymer.
[0198] 15. The method of any one of embodiments 1 to 14, wherein the heating step is performed by autoclaving the contact lens precursor having carboxylic acid groups thereon immersed in the aqueous solution, which is a packaging solution in a sealed lens package, at a temperature of about 115° C. to about 125° C. for about 30-90 minutes.
[0199] 16. A contact lens comprising: an anterior surface, an opposite posterior surface, and a layered structural configuration from the anterior surface to the posterior surface, wherein the layered structural configuration comprises an outer anterior surface hydrogel layer, an inner layer, and an outer posterior surface hydrogel layer, wherein the inner layer comprises a lens bulk material and has carboxylic acid groups on and / or near a surface of the inner layer, wherein the outer anterior surface hydrogel layer and the outer posterior surface hydrogel layer comprise a cross-linked polymer material comprising polymer chains derived from a hydrophilic copolymer comprising monomer units of: (a) at least one epoxy-containing The invention relates to a contact lens comprising: (a) a vinyl monomer having a carboxylic acid group, (b) at least one amino group-containing vinyl monomer having a primary or secondary amino group, (c) at least one polyethylene glycol-containing vinyl monomer, and (d) at least one phosphorylcholine-containing vinyl monomer, wherein the sum of the amounts of components (a) and (b) in the at least one hydrophilic copolymer is about 40% or less by mole, wherein the outer front surface hydrogel layer and the outer back surface hydrogel layer are covalently attached to the inner layer through bonds each formed between a carboxylic acid group and an epoxy group, wherein the contact lens has a water break up time (WBUT) of at least 10 seconds.
[0200] 17. The contact lens of embodiment 16, wherein the inner layer is comprised of a lens bulk material having carboxylic acid groups on and / or near a surface of the bulk material.
[0201] 18. The contact lens of embodiment 16, wherein the inner layer comprises a layer of lens bulk material and at least one polymer material having carboxylic acid groups.
[0202] 19. The method of any one of embodiments 1 to 15 or the contact lens of any one of embodiments 16 to 18, wherein the at least one hydrophilic copolymer comprises:
[0203] (a) at least one having the formula Monomer units of epoxy-containing vinyl monomers;
[0204] (b) at least one having the formula Monomer units of amino-containing acrylic monomers;
[0205] (c) at least one having the formula Monomer units of polyethylene glycol-containing acrylic monomers; and
[0206] (d) at least one having the formula The monomer unit of the phosphorylcholine-containing acrylic monomer,
[0207] in:
[0208] Each R0 is independently H or CH3; each R0' is independently H or C1-C4 alkyl; B1, B2 and B3 are independently O or NR'; R' is H or C1-C4 alkyl; D1, D2 and D3 are independently C1-C 12 Alkylene divalent group; D0 is C1-C 12 An alkylene divalent group or a divalent group of -D4-O-D5-B4-CH2-; B4 is -O- or D4 is C1-C 12 Alkylene divalent group; D5 is a C2-C6 alkylene divalent group or D6 and D7 are independently C2-C6 alkylene divalent groups; d1 is 0, 1 or 2; PEG is A polyethylene glycol group, wherein R" is H or a C1-C4 alkyl group; t2 is an integer from 3 to 100; PC is A zwitterionic group, wherein t1 is an integer from 1 to 5, and 1 R. 2 R and 3 R is independently C1-C8 alkyl or C1-C8 hydroxyalkyl.
[0209] 20. The method of any one of embodiments 1 to 15 or the contact lens of any one of embodiments 16 to 18, wherein the at least one hydrophilic copolymer is a statistical copolymer having formula (I),
[0210]
[0211] in
[0212] T' and T" are independently H or a terminal group; each R0 is independently H or CH3; each R0' is independently H or a C1-C4 alkyl group; B1, B2 and B3 are independently O or NR'; R' is H or a C1-C4 alkyl group; D1, D2 and D3 are independently C1-C 12 Alkylene divalent group; D0 is C1-C 12 An alkylene divalent group or a divalent group of -D4-O-D5-B4-CH2-; B4 is -O- or D4 is C1-C 12 Alkylene divalent group; D5 is a C2-C6 alkylene divalent group or D6 and D7 are independently C2-C6 alkylene divalent groups; d1 is 0, 1 or 2; PEG is A polyethylene glycol group, wherein R" is H or a C1-C4 alkyl group; t2 is an integer from 3 to 100; PC is A zwitterionic group, wherein t1 is an integer from 1 to 5, and 1 R. 2 R and 3 R is independently C1-C8 alkyl or C1-C8 hydroxyalkyl; a, b, c, and d are independently integers from 5 to 100, wherein (a+c) / (a+b+c+d)≤0.40 (preferably ≤0.35, more preferably ≤0.30, even more preferably ≤0.25).
[0213] 21. The method or contact lens of embodiment 20, wherein in formula (I), a / c is 10 to 0.1.
[0214] 22. The method or contact lens of embodiment 20, wherein in formula (I), a / c is 5 to 0.2.
[0215] 23. The method or contact lens of embodiment 20, wherein in formula (I), a / c is 2.5 to 0.4.
[0216] 24. The method or contact lens of embodiment 20, wherein in formula (I), a / c is 2 to 0.5.
[0217] 25. The method of any one of embodiments 1 to 15 and 19 to 24 or the contact lens of any one of embodiments 16 to 24, wherein the sum of the amounts of components (a) and (b) in the at least one hydrophilic copolymer is about 35% or less by mole.
[0218] 26. The method of any one of embodiments 1 to 15 and 19 to 24 or the contact lens of any one of embodiments 16 to 24, wherein the sum of the amounts of components (a) and (b) in the at least one hydrophilic copolymer is about 30% or less by mole.
[0219] 27. The method of any one of embodiments 1 to 15 and 19 to 24 or the contact lens of any one of embodiments 16 to 24, wherein the sum of the amounts of components (a) and (b) in the at least one hydrophilic copolymer is about 25% or less by mole.
[0220] 28. The method of any one of embodiments 1 to 15 and 19 to 27 or the contact lens of any one of embodiments 16 to 27, wherein the lens body material is a hard plastic material.
[0221] 29. The method or contact lens of embodiment 28, wherein the hard plastic material is a cross-linked polymethacrylate.
[0222] 30. The method of any one of embodiments 1 to 15 and 19 to 27 or the contact lens of any one of embodiments 16 to 27, wherein the lens body material is a rigid gas permeable lens material.
[0223] 31. The method of any one of Examples 1 to 15 and 19 to 27 or the contact lens of any one of Examples 16 to 27, wherein the lens body material consists essentially of a central optical zone and a peripheral zone, the central optical zone being essentially made of a gas permeable lens material and the peripheral zone being essentially made of a non-silicone hydrogel material having an equilibrium water content of about 10% to 80% by weight.
[0224] 32. The method of any one of Examples 1 to 15 and 19 to 27 or the contact lens of any one of Examples 16 to 27, wherein the lens body material consists essentially of a 3-dimensional article and a non-silicone hydrogel material, wherein the 3-dimensional article is made of a non-hydrogel material and has a three-dimensional size smaller than that of the contact lens so that the 3-dimensional article is completely embedded in the non-silicone hydrogel material having an equilibrium water content of approximately 10% to 80% by weight.
[0225] 33. The method of any one of embodiments 1 to 15 and 19 to 27 or the contact lens of any one of embodiments 16 to 27, wherein the lens bulk material is a non-silicone hydrogel material having an equilibrium water content of about 10% to 80% by weight.
[0226] 34. The method or contact lens of any one of embodiments 31 to 33, wherein the non-silicone hydrogel material comprises at least 50% by mole of repeating units of at least one hydroxyl-containing vinylic monomer.
[0227] 35. The method or contact lens of embodiment 34, wherein the at least one hydroxyl-containing vinyl monomer is selected from the group consisting of hydroxyethyl (meth)acrylate, glycerol (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-amino-2-hydroxypropyl (meth)acrylate, N-2-hydroxyethyl (meth)acrylamide, N-3-hydroxypropyl (meth)acrylamide, N-2-hydroxypropyl (meth)acrylamide, N-2,3-dihydroxypropyl (meth)acrylamide, N-tris (hydroxymethyl)methyl (meth)acrylamide, vinyl alcohol, allyl alcohol, and combinations thereof.
[0228] 36. The method or contact lens of embodiment 34, wherein the at least one hydroxyl-containing vinylic monomer is selected from the group consisting of hydroxyethyl (meth)acrylate, glycerol (meth)acrylate, and vinyl alcohol.
[0229] 37. The method of any one of embodiments 1 to 15 and 19 to 27 or the contact lens of any one of embodiments 31 to 36, wherein the lens bulk material is a silicone hydrogel material.
[0230] 38. The method of any one of Examples 1 to 15 and 19 to 27 or the contact lens of any one of Examples 16 to 27, wherein the lens body material consists essentially of a central optical zone, which is essentially made of rigid gas permeable lens material and is surrounded by a peripheral zone essentially made of silicone hydrogel material.
[0231] 39. A method as described in any of Examples 1 to 15 and 19 to 27 or a coated contact lens as described in any of Examples 16 to 27, wherein the lens body material consists essentially of a 3-dimensional article and a silicone hydrogel material, wherein the 3-dimensional article is made of a non-hydrogel material and has a smaller 3-dimensional size than the preformed embedded contact lens so that the 3-dimensional article is completely embedded in the silicone hydrogel material.
[0232] 40. The method or contact lens of any one of embodiments 37 to 39, wherein the silicone hydrogel material comprises repeating units of at least one hydrophilic vinylic monomer, repeating units of at least one siloxane-containing vinylic monomer, and repeating units of at least one vinylic cross-linking agent.
[0233] 41. A method or contact lens as described in Example 40, wherein the at least one hydrophilic vinyl monomer comprises: (1) an alkyl (meth) acrylamide selected from the group consisting of (meth) acrylamide, N,N-dimethyl (meth) acrylamide, N-ethyl (meth) acrylamide, N,N-diethyl (meth) acrylamide, N-propyl (meth) acrylamide, N-isopropyl (meth) acrylamide, N-3-methoxypropyl (meth) acrylamide, and combinations thereof; (2) a hydroxyl-containing acrylic monomer selected from the group consisting of N-2-hydroxyethyl (meth) acrylamide, N,N-bis (hydroxyethyl) (meth) acrylamide, N-3-hydroxypropyl (meth) acrylamide , N-2-hydroxypropyl (meth)acrylamide, N-2,3-dihydroxypropyl (meth)acrylamide, N-tris(hydroxymethyl)methyl (meth)acrylamide, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, glycerol methacrylate, di(ethylene glycol) (meth)acrylate, tri(ethylene glycol) (meth)acrylate, tetra(ethylene glycol) (meth)acrylate, poly(ethylene glycol) (meth)acrylate having a number average molecular weight of up to 1500, poly(ethylene glycol)ethyl (meth)acrylamide having a number average molecular weight of up to 1500, and combinations thereof; (3) a carboxyl-containing acrylic monomer selected from the group consisting of: 2-(Meth)acrylamidoglycolic acid, (meth)acrylic acid, ethylacrylic acid, 3-(meth)acrylamidopropionic acid, 5-(meth)acrylamidopentanoic acid, 4-(meth)acrylamidobutyric acid, 3-(meth)acrylamido-2-methylbutyric acid, 3-(meth)acrylamido-3-methylbutyric acid, 2-(meth)acrylamido-2-methyl-3,3-dimethylbutyric acid, 3-(meth)acrylamidohexanoic acid, 4-(meth)acrylamido-3,3-dimethylhexanoic acid, and combinations thereof; (4) amino group-containing acrylic monomers selected from the group consisting of N-2-aminoethyl (meth)acrylamide, N-2-methylaminoethyl (meth)acrylamide, N-2- Ethylaminoethyl (meth)acrylamide, N-2-dimethylamino-ethyl (meth)acrylamide, N-3-aminopropyl (meth)acrylamide, N-3-methylaminopropyl (meth)acrylamide, N-3-dimethylaminopropyl (meth)acrylamide, 2-aminoethyl (meth)acrylate, 2-methylaminoethyl (meth)acrylate, 2-ethylaminoethyl (meth)acrylate, 3-aminopropyl (meth)acrylate, 3-methylaminopropyl (meth)acrylate, 3-ethylaminopropyl (meth)acrylate, 3-amino-2-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate trimethylammonium hydrochloride, dimethylaminoethyl (meth)acrylate, and combinations thereof;(5) N-vinyl amide monomers selected from the group consisting of N-vinyl pyrrolidone, N-vinyl-3-methyl-2-pyrrolidone, N-vinyl-4-methyl-2-pyrrolidone, N-vinyl-5-methyl-2-pyrrolidone, N-vinyl-6-methyl-2-pyrrolidone, N-vinyl-3-ethyl-2-pyrrolidone, N-vinyl-4,5-dimethyl-2-pyrrolidone, N-vinyl-5,5-dimethyl-2-pyrrolidone, N-vinyl-3,3,5-trimethyl-2-pyrrolidone, N-vinyl piperidone, N-vinyl-3-methyl-2-piperidone, N-vinyl-4-methyl-2-piperidone, N-vinyl-5-methyl-2-piperidone, ketone, N-vinyl-6-methyl-2-piperidone, N-vinyl-6-ethyl-2-piperidone, N-vinyl-3,5-dimethyl-2-piperidone, N-vinyl-4,4-dimethyl-2-piperidone, N-vinyl caprolactam, N-vinyl-3-methyl-2-caprolactam, N-vinyl-4-methyl-2-caprolactam, N-vinyl-7-methyl-2-caprolactam, N-vinyl-7-ethyl-2-caprolactam, N-vinyl-3,5-dimethyl-2-caprolactam, N-vinyl-4,6-dimethyl-2-caprolactam, N-vinyl-3,5,7-trimethyl-2-caprolactam, N-vinyl-N-methylacetamide, N-vinylformamide, N-vinyl acetamide, N-vinyl isopropylamide, N-vinyl-N-ethyl acetamide, N-vinyl-N-ethyl formamide, and mixtures thereof; (6) a methylene-containing pyrrolidone monomer selected from the group consisting of 1-methyl-3-methylene-2-pyrrolidone, 1-ethyl-3-methylene-2-pyrrolidone, 1-methyl-5-methylene-2-pyrrolidone, 1-ethyl-5-methylene-2-pyrrolidone, 5-methyl-3-methylene-2-pyrrolidone, 5-ethyl-3-methylene-2-pyrrolidone, 1-n-propyl-3-methylene-2-pyrrolidone, 1-n-propyl-5-methylene-2-pyrrolidone, 1-isopropyl-3-methylene-2-pyrrolidone, 1- Isopropyl-5-methylene-2-pyrrolidone, 1-n-butyl-3-methylene-2-pyrrolidone, 1-tert-butyl-3-methylene-2-pyrrolidone, and combinations thereof; (7) acrylic monomers having a C1-C4 alkoxyethoxy group and selected from the group consisting of ethylene glycol methyl ether (meth)acrylate, di(ethylene glycol) methyl ether (meth)acrylate, tri(ethylene glycol) methyl ether (meth)acrylate, tetra(ethylene glycol) methyl ether (meth)acrylate, C1-C4-alkoxy poly(ethylene glycol) (meth)acrylate having a number average molecular weight of up to 1500, methoxy-poly(ethylene glycol)ethyl (meth)acrylamide having a number average molecular weight of up to 1500, and combinations thereof;(8) a vinyl ether monomer selected from the group consisting of ethylene glycol monovinyl ether, di(ethylene glycol) monovinyl ether, tri(ethylene glycol) monovinyl ether, tetra(ethylene glycol) monovinyl ether, poly(ethylene glycol) monovinyl ether, ethylene glycol methyl vinyl ether, di(ethylene glycol) methyl vinyl ether, tri(ethylene glycol) methyl vinyl ether, tetra(ethylene glycol) methyl vinyl ether, poly(ethylene glycol) methyl vinyl ether, and combinations thereof; (9) an allyl ether monomer selected from the group consisting of ethylene glycol monoallyl ether, di(ethylene glycol) monoallyl ether, tri(ethylene glycol) monoallyl ether, tetra(ethylene glycol) monoallyl ether, poly(ethylene glycol) monoallyl ether, ethylene glycol methyl allyl ether, di(ethylene glycol) methyl allyl ether, tri(ethylene glycol) monoallyl ether, tetra(ethylene glycol) monoallyl ether, poly(ethylene glycol) monoallyl ether, (10) a vinyl monomer containing phosphorylcholine selected from the group consisting of (meth)acryloyloxyethyl phosphorylcholine, (meth)acryloyloxypropyl phosphorylcholine, 4-((meth)acryloyloxy)butyl 2'-(trimethylammonio)ethyl phosphate, 2-[(meth)acryloylamino]ethyl 2'-(trimethylammonio)-ethyl phosphate, 3-[(meth)acryloylamino]propyl 2'-(trimethylammonio)ethyl phosphate, 4-[(meth)acryloylamino]butyl 2'-(trimethylammonio)ethyl phosphate, 5-((meth)acryloyloxy)pentyl 2'-(trimethylammonio)ethyl phosphate, 6-((meth)acryloyloxy)hexyl 2'-(trimethylammonio)ethyl phosphate, 2-((meth)acryloyloxy)ethyl phosphate 2'-(triethylammonio)ethyl phosphate, 2-((meth)acryloyloxy)ethyl phosphate 2'-(tripropylammonio)ethyl phosphate, 2-((meth)acryloyloxy)ethyl phosphate 2'-(tributylammonio)ethyl phosphate, 2-((meth)acryloyloxy)propyl phosphate 2'-(trimethylammonio)ethyl phosphate, 2-((meth)acryloyloxy)butyl phosphate 2'-(trimethylammonio)ethyl phosphate, 2-((meth)acryloyloxy)pentyl phosphate 2'-(trimethylammonio)ethyl phosphate, 2-((meth)acryloyloxy)hexyl 2'-(trimethylammonio)ethyl phosphate esters, 2-(vinyloxy)ethyl 2'-(trimethylammonio)ethyl phosphate, 2-(allyloxy)ethyl 2'-(trimethylammonio)ethyl phosphate, 2-(vinyloxycarbonyl)ethyl 2'-(trimethylammonio)ethyl phosphate, 2-(allyloxycarbonyl)ethyl 2'-(trimethylammonio)-ethyl phosphate, 2-(vinylcarbonylamino)ethyl 2'-(trimethylammonio)ethyl phosphate, 2-(allyloxycarbonylamino)ethyl 2'-(trimethylammonio)ethyl phosphate, 2-(butenoyloxy)ethyl 2'-(trimethylammonio)ethyl phosphate, and combinations thereof; (11) allyl alcohol; (12) N-2-hydroxyethyl vinylcarbamate; (13) N-carboxyvinyl-β-alanine;(14) N-carboxyvinyl-α-alanine; (15) or a combination thereof;
[0234] 42. The method or contact lens of embodiment 40 or 41, wherein the at least one siloxane-containing vinyl monomer is selected from the group consisting of: α-(meth)acryloxypropyl-terminated ω-C1-C4-alkyl-terminated polydimethylsiloxane, α-(meth)acryloxy-2-hydroxypropoxypropyl-terminated ω-C1-C4-alkyl-terminated polydimethylsiloxane, α-(2-hydroxy-methacryloxypropoxypropyl)-ω-C1-C4-alkyl-decamethylpentasiloxane, α-[3-(meth)acryloxyethoxy-2-hydroxypropoxypropyl]-terminated ω-C1-C4-alkyl-terminated polydimethylsiloxane, α-[3-(meth)acryloxy-propoxy-2-hydroxy α-[3-(meth)acryloyloxyethylamino-2-hydroxypropoxypropyl]-capped ω-C1-C4-alkyl-capped polydimethylsiloxane, α-[3-(meth)acryloyloxyisopropoxy-2-hydroxypropoxypropyl]-capped ω-C1-C4-alkyl-capped polydimethylsiloxane, α-[3-(meth)acryloyloxybutoxy-2-hydroxypropoxypropyl]-capped ω-C1-C4-alkyl-capped polydimethylsiloxane, α-[3-(meth)acryloyloxyethylamino-2-hydroxypropoxypropyl]-capped ω-C1-C4-alkyl-capped polydimethylsiloxane, α-[3-(meth)acryloyloxypropylamino-2-hydroxypropoxypropyl]-capped ω-C1-C4-alkyl-capped polydimethylsiloxane, α-[3-(meth)acryloyloxypropylamino-2-hydroxypropoxypropyl]-capped ω-C1-C4-alkyl-capped polydimethylsiloxane, [(meth)acryloyloxy-butylamino-2-hydroxypropoxypropyl]-terminated ω-C1-C4-alkyl-terminated polydimethylsiloxane, [(meth)acryloyloxy(polyethyleneoxy)-2-hydroxypropoxypropyl]-terminated ω-C1-C4-alkyl-terminated polydimethylsiloxane, [(meth)acryloyloxy-2-hydroxypropoxy-ethoxypropyl]-terminated ω-C1-C4-alkyl-terminated polydimethylsiloxane, [(meth)acryloyloxy-2-hydroxypropyl-N-ethylaminopropyl]-terminated ω-C1-C4-alkyl-terminated polydimethylsiloxane, [(meth)acryloyloxy-2-hydroxypropyl-aminopropyl]-terminated ω-C1-C4-alkyl-terminated polydimethylsiloxane Siloxane, ω-C1-C4-alkyl-terminated polydimethylsiloxane terminated by α-[(meth)acryloyloxy-2-hydroxypropoxy-(polyethyleneoxy)propyl], ω-C1-C4-alkyl-terminated polydimethylsiloxane terminated by α-(meth)acryloylaminopropoxypropyl, ω-C1-C4-alkyl-terminated polydimethylsiloxane terminated by α-N-methyl-(meth)acryloylaminopropoxypropyl, ω-C1-C4-alkyl-terminated polydimethylsiloxane terminated by α-[3-(meth)acrylamidoethoxy-2-hydroxypropoxy-propyl], ω-C1-C4-alkyl-terminated polydimethylsiloxane terminated by α-[3-(meth)acrylamidopropoxy-2-hydroxypropoxypropyl],α-[3-(Meth)acrylamide isopropoxy-2-hydroxypropoxypropyl]-terminated ω-C1-C4-alkyl-terminated polydimethylsiloxane, α-[3-(Meth)acrylamide butoxy-2-hydroxypropoxypropyl]-terminated ω-C1-C4-alkyl-terminated polydimethylsiloxane, α-[3-(Meth)acrylamide-2-hydroxypropoxypropyl]-terminated ω-C1-C4-alkyl polydimethylsiloxane, α-[3-[N-methyl-(meth)acrylamide]-2-hydroxypropoxypropyl]-terminated ω-C1-C4-alkyl-terminated End-capped polydimethylsiloxane, N-methyl-N'-(propyl tetra(dimethylsiloxy)dimethylbutylsilane)(meth)acrylamide, N-(2,3-dihydroxypropane)-N'-(propyl tetra(dimethylsiloxy)dimethylbutylsilane)(meth)acrylamide, (meth)acrylamidopropyl tetra(dimethylsiloxy)dimethylbutylsilane, α-vinyl carbonate-capped ω-C1-C4-alkyl-capped polydimethylsiloxane, α-vinyl carbamate-capped ω-C1-C4-alkyl-capped polydimethylsiloxane, and mixtures thereof.
[0235] 43. The method or contact lens of embodiment 40 or 41, wherein the at least one siloxane-containing vinyl monomer is selected from the group consisting of a vinyl monomer having a bis(trialkylsilyloxy)alkylsilyl group, a vinyl monomer having a tri(trialkylsilyloxy)silyl group, a polysiloxane vinyl monomer, 3-methacryloxypropylpentamethyldisiloxane, tert-butyldimethyl-siloxyethyl carbonate vinyl ester, trimethylsilylethyl carbonate vinyl ester, and trimethylsilylmethyl carbonate vinyl ester, and combinations thereof.
[0236] 44. The method or contact lens of embodiment 40 or 41, wherein the at least one siloxane-containing vinylic monomer comprises at least one vinylic monomer having formula (M1) or (M2)
[0237]
[0238] Among them: a M1 is zero or 1; R M0 is H or methyl; X M0 Is O or NR M1 ; L M1 is a C2-C8 alkylene divalent group or -K M1′ -X M1 -L M1″ -、 -L M1′ -X M1′ -CH2-CH(OH)-CH2-OLM1″ -,or The divalent group of L M1 ' is a C2-C8 alkylene divalent group having zero or one hydroxyl group; L M1 " is a C3-C8 alkylene divalent group having zero or one hydroxyl group; X M1 Yes O, NR M1 、NHCOO、OCONH、CONR M1 , or NR M1 CO;R M1 is H or a C1-C4 alkyl group having 0 to 2 hydroxyl groups; R t1 and R t2 are independently C1-C6 alkyl; X M1 ' is O or NR M1 ; v1 is an integer from 1 to 30; m2 is an integer from 0 to 30; n1 is an integer from 3 to 40; and r1 is an integer from 2 or 3.
[0239] 45. The method or contact lens of embodiment 40 or 41, wherein the at least one siloxane-containing vinyl monomer comprises tris(trimethylsilyloxy)silylpropyl(meth)acrylate, [3-(meth)acryloxy-2-hydroxypropoxy]propylbis(trimethylsiloxy)methylsilane, [3-(meth)acryloxy-2-hydroxypropoxy]propylbis(trimethylsiloxy)butylsilane, 3-(meth)acryloxy-2-(2-hydroxyethoxy)-propoxy)propylbis(trimethylsiloxy)methylsilane, 3-(meth)acryloxy-2-hydroxypropoxy)propyltri(trimethylsiloxy)propyltri(trimethylsiloxy)methylsilane, (Trimethylsilyloxy) silane, N-[tris(trimethylsilyloxy) silylpropyl]-(meth)acrylamide, N-(2-hydroxy-3-(3-(bis(trimethylsilyloxy)methylsilyl)propoxy)propyl)-2-methyl(meth)acrylamide, N-(2-hydroxy-3-(3-(bis(trimethylsilyloxy)methylsilyl)propoxy)propyl)(meth)acrylamide, N-(2-hydroxy-3-(3-(tris(trimethylsilyloxy)silyl)propoxy)propyl)-2-methylacrylamide, N-(2-hydroxy-3-(3-(tris(trimethylsilyloxy)silyl)propoxy)propyl)-2-methylacrylamide, (meth)acrylamide, N-[tris(dimethylpropylsilyloxy)silylpropyl]-(meth)acrylamide, N-[tris(dimethylphenylsilyloxy)-silylpropyl]-(meth)acrylamide, N-[tris(dimethylethylsilyloxy)-silylpropyl]-(meth)acrylamide, N,N-bis[2-hydroxy-3-(3-(bis(trimethylsilyloxy)methylsilyl)-propoxy)propyl]-2-methyl(meth)acrylamide, N,N-bis[2-hydroxy-3-(3-(bis(trimethylsilyloxy)methylsilyl)-propoxy)propyl]-2-methyl(meth)acrylamide, alkyl) propoxy)-propyl] (meth) acrylamide, N,N-bis[2-hydroxy-3-(3-(tris(trimethylsilyloxy)silyl) propoxy)propyl]-2-methyl(meth) acrylamide, N,N-bis[2-hydroxy-3-(3-(tris(trimethylsilyloxy)silyl) propoxy)propyl] (meth) acrylamide, N-[2-hydroxy-3-(3-(tert-butyldimethylsilyl) propoxy)-propyl]-2-methyl(meth) acrylamide, N-[2-hydroxy-3-(3-(tert-butyldimethylsilyl) propoxy)-propyl] (meth) acrylamide, N,N-bis[2-hydroxy-3-(3-(tert-butyldimethylsilyl)propoxy)propyl]-2-methyl(meth)acrylamide, N-2-(meth)acryloyloxyethyl-O-(methyl-bis-trimethylsiloxy-3-propyl)silylcarbamate, 3-(trimethylsilyl)propylvinyl carbonate, 3-(vinyloxycarbonylthio)-propyl-tris(trimethyl-siloxy)silane, 3-[tris(trimethylsiloxy)silyl]propylvinylcarbamate, 3-[tris(trimethylsiloxy)silyl]propylcarbamate allyl, 3-[tris(trimethylsiloxy)silyl]propylvinyl carbonate, or a combination thereof.
[0240] 46. The method or contact lens of any one of embodiments 40 to 45, wherein the at least one ethylenic cross-linking agent comprises at least one polysiloxane ethylenic cross-linking agent.
[0241] 47. The method or contact lens of embodiment 46, wherein the at least one polysiloxane vinyl crosslinker comprises a di-(meth)acryloyloxy-terminated polysiloxane vinyl crosslinker having dimethylsiloxane units and monovalent C4-C4-C4-(meth)acryloyloxy-terminated crosslinkers each having one methyl substituent and one ... 40 The hydrophilic siloxane unit is substituted with an organic group.
[0242] 48. The method or contact lens of Example 46, wherein the at least one polysiloxane vinyl crosslinker comprises at least one hydrophilized polysiloxane vinyl crosslinker having formula (G):
[0243]
[0244] in:
[0245] d1 is an integer from 30 to 500, and d2 is an integer from 1 to 75, with the proviso that d2 / d1 is from about 0.035 to about 0.15;
[0246] X 01 Is O or NR IN , where R IN is hydrogen or C1-C 10 -alkyl;
[0247] R I0 is hydrogen or methyl;
[0248] R I1 and R I2 are independently substituted or unsubstituted C1-C 10 Alkylene divalent group or -R I4 -OR I5 - a divalent group, wherein RI4 and R I5 are independently substituted or unsubstituted C1-C 10 Alkylene divalent group;
[0249] R I3 is a monovalent group having any one of formulae (G-1) to (G-5)
[0250]
[0251] k1 is 0 or 1; m1 is an integer from 2 to 4; m2 is an integer from 1 to 5; m3 is an integer from 3 to 6; m4 is an integer from 2 to 5;
[0252] R I6 is hydrogen or methyl;
[0253] R I7 is a C2-C6 hydrocarbon group having a valence of (m2+1);
[0254] R I8 is a C2-C6 hydrocarbon group having a valence of (m4+1);
[0255] R I9 is ethyl or hydroxymethyl;
[0256] R I10 is methyl or hydroxymethyl;
[0257] R I11 is hydroxy or methoxy;
[0258] X I1 Is -S-sulfide bond or -NR I12 - tertiary amino bond, where R I12 is C1-C1 alkyl, hydroxyethyl, hydroxypropyl or 2,3-dihydroxypropyl; and
[0259] X I2 yes Amide bond, where R I13 is hydrogen or C1-C 10 alkyl.
[0260] 49. The method or contact lens of Example 46, wherein the at least one polysiloxane vinyl crosslinker comprises: (i) a vinyl crosslinker comprising a sole polydiorganosiloxane segment and two terminal ethylenically unsaturated groups selected from the group consisting of (meth)acryloyloxy, (meth)acryloylamino, vinyl carbonate, vinyl carbamate groups; and / or (ii) an extended polysiloxane vinyl crosslinker comprising at least two polydiorganosiloxane segments and a covalent linker between each pair of polydiorganosiloxane segments and two terminal ethylenically unsaturated groups selected from the group consisting of (meth)acryloyloxy, (meth)acryloylamino, vinyl carbonate, vinyl carbamate groups.
[0261] 50. The method or contact lens of Example 46, wherein the at least one polysiloxane vinyl crosslinker comprises α,ω-bis[3-(meth)acrylamidopropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxy-2-hydroxypropoxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxyethoxy-2-hydroxypropoxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxypropoxy-2-hydroxypropoxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxyisopropoxy- 2-hydroxypropoxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxybutoxy-2-hydroxypropoxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxyethoxy-2-hydroxypropoxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acrylamideethoxy-2-hydroxypropoxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acrylamidepropoxy-2-hydroxypropoxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acrylamideisopropoxy-2-hydroxypropoxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acrylamidebutoxy-2-hydroxypropoxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxy α,ω-bis[3-(meth)acryloxypropylamino-2-hydroxypropoxypropyl]-terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxybutylamino-2-hydroxypropoxypropyl]-terminated polydimethylsiloxane, α,ω-bis[(meth)acrylamideethylamino-2-hydroxypropoxy-propyl]-terminated polydimethylsiloxane, α,ω-bis[3-(meth)acrylamide-butylamino-2-hydroxypropoxypropyl]-terminated polydimethylsiloxane, α,ω-bis[(meth)acrylamideethylamino-2-hydroxypropoxy-propyl]-terminated polydimethylsiloxane, α,ω-bis[3-(meth)acrylamide-propylamino-2-hydroxypropoxypropyl]-terminated polydimethylsiloxane, α,ω-bis[3-(meth)acrylamide-butylamino-2-hydroxypropoxypropyl]-terminated polydimethylsiloxane, α,ω-bis[(meth)acryloxy-2-hydroxypropyl-N-ethylaminopropyl] terminated polydimethylsiloxane, α,ω-bis[(meth)acryloxy-2-hydroxypropyl-aminopropyl]-polydimethylsiloxane, α,ω-bis[(meth)acryloxy-2-hydroxypropyloxy-(polyethyleneoxy)propyl] terminated polydimethylsiloxane, α,ω-bis[(meth)acryloxyethylamino-carbonyloxy-ethoxypropyl] terminated polydimethylsiloxane, α,ω-bis[(meth)acryloxyethylamino-carbonyloxy-(polyethyleneoxy)propyl] terminated polydimethylsiloxane, or a combination thereof.
[0262] 51. The contact lens method of any one of embodiments 40 to 50, wherein the at least one ethylenic cross-linking agent comprises at least one non-silicone ethylenic cross-linking agent.
[0263] 52. The method or contact lens of embodiment 51, wherein the at least one non-silicone vinyl crosslinker comprises ethylene glycol di-(meth)acrylate, diethylene glycol di-(meth)acrylate, triethylene glycol di-(meth)acrylate, tetraethylene glycol di-(meth)acrylate, glycerol di-(meth)acrylate, 1,3-propylene glycol di-(meth)acrylate, 1,3-butylene glycol di-(meth)acrylate, 1,4-butylene glycol di-(meth)acrylate, glycerol 1,3-diglycerate di-(meth)acrylate, ethylene bis[oxy(2-hydroxypropane-1,3-diyl)] di-(meth)acrylate, bis[2-(meth)acryloyloxyethyl] phosphate, trimethylolpropane di-(meth)acrylate, and 3,4-bis[(meth)acryloyl]tetrahydrofuran, diacrylamide, dimethylacrylamide, N,N-di(meth)acryloyl-N-methylamine, N,N-di(meth)acryloyl-N-ethylamine, N,N'-methylenebis(meth)acrylamide, N,N'-ethylenebis(meth)acrylamide, N,N'-dihydroxyethylenebis(meth)acrylamide, N,N'-propylenebis(meth)acrylamide, N,N'-2-hydroxypropylenebis(meth)acrylamide, N,N'-2,3-dihydroxybutylenebis(meth)acrylamide, 1,3-bis(meth)acrylamide dihydrogen phosphate amidopropane-2-yl ester, piperazine diacrylamide, tetraethylene glycol divinyl ether, triethylene glycol divinyl ether, diethylene glycol divinyl ether, ethylene glycol divinyl ether, triallyl isocyanurate, triallyl cyanurate, trimethylolpropane trimethacrylate, pentaerythritol tetramethacrylate, bisphenol A dimethacrylate, allyl methacrylate, allyl acrylate, N-allyl-methacrylamide, N-allyl-acrylamide, or a combination thereof.
[0264] 53. The method or contact lens of any one of embodiments 40 to 52, wherein the silicone hydrogel comprises repeating units of at least one blended vinylic monomer.
[0265] 54. The method or contact lens of Example 53, wherein the at least one blended vinyl monomer comprises (meth)acrylic acid C1-C 10Alkyl esters, cyclopentyl acrylate, cyclohexyl methacrylate, cyclohexyl acrylate, isobornyl (meth)acrylate, styrene, 2,4,6-trimethylstyrene (TMS), tert-butylstyrene (TBS), trifluoroethyl (meth)acrylate, hexafluoro-isopropyl (meth)acrylate, hexafluorobutyl (meth)acrylate, or a combination thereof.
[0266] 55. The method or contact lens of Embodiment 53 wherein the at least one blended vinylic monomer comprises methyl methacrylate.
[0267] 56. The method or contact lens of any one of embodiments 40 to 55, wherein the at least one hydrophilic vinyl monomer comprises at least one hydrophilic N-vinyl amide monomer selected from the group consisting of N-vinyl pyrrolidone, N-vinyl piperidone, N-vinyl caprolactam, N-vinyl-N-methylacetamide, N-vinyl formamide, N-vinyl acetamide, N-vinyl isopropyl amide, N-vinyl-N-methylacetamide, N-vinyl-N-ethylacetamide, N-vinyl-N-ethylformamide, and mixtures thereof.
[0268] 57. The method or contact lens of any one of embodiments 40 to 55 wherein the at least one hydrophilic vinyl monomer comprises N-vinyl pyrrolidone and / or N-vinyl-N-methylacetamide.
[0269] 58. The method or contact lens of any one of embodiments 40 to 57, wherein the at least one hydrophilic vinyl monomer comprises a hydrophilic (meth)acrylamide-based monomer selected from the group consisting of (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N-ethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N-propyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-3-methoxypropyl (meth)acrylamide, N-2-hydroxyethyl (meth)acrylamide, N,N-bis (hydroxyethyl) (meth)acrylamide, N-3-hydroxypropyl (meth)acrylamide, N-2-hydroxypropyl (meth)acrylamide, N-2,3-dihydroxypropyl (meth)acrylamide, N-tris (hydroxymethyl)methyl (meth)acrylamide, poly (ethylene glycol) ethyl (meth)acrylamide having a number average molecular weight of up to 1500, 2- (meth)acrylamidoethyl (meth)acrylamide, alkyd, 3-(meth)acrylamidopropionic acid, 5-(meth)acrylamidopentanoic acid, 4-(meth)acrylamidobutyric acid, 3-(meth)acrylamido-2-methylbutyric acid, 3-(meth)acrylamido-3-methylbutyric acid, 2-(meth)acrylamido-2-methyl-3,3-dimethylbutyric acid, 3-(meth)acrylamidohexanoic acid, 4-(meth)acrylamido-3,3-dimethylhexanoic acid, N-2-aminoethyl(meth)acrylamide, N-2-methylaminoethyl(meth)acrylamide, N-2-ethylaminoethyl(meth)acrylamide, N-2-dimethylaminoethyl(meth)acrylamide, N-3-aminopropyl(meth)acrylamide, N-3-methylaminopropyl(meth)acrylamide, N-3-dimethylaminopropyl(meth)acrylamide, methoxy-poly(ethylene glycol)ethyl(meth)acrylamide having a number average molecular weight of up to 1500, and combinations thereof.
[0270] 59. The method or contact lens of any one of embodiments 40 to 57, wherein the at least one hydrophilic vinyl monomer comprises a hydrophilic (meth)acrylamide-based monomer selected from the group consisting of (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-propyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-3-methoxypropyl(meth)acrylamide, N-2-hydroxyethyl(meth)acrylamide, N-3-hydroxypropyl(meth)acrylamide, and combinations thereof.
[0271] 60. A method or contact lens as described in any of Examples 40 to 59, wherein the at least one hydrophilic vinyl monomer comprises a hydroxyl-containing vinyl monomer selected from the group consisting of hydroxyethyl (meth)acrylate, glycerol (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-amino-2-hydroxypropyl (meth)acrylate, N-2-hydroxyethyl (meth)acrylamide, N-3-hydroxypropyl (meth)acrylamide, N-2-hydroxypropyl (meth)acrylamide, N-2,3-dihydroxypropyl (meth)acrylamide, N-tris (hydroxymethyl) methyl (meth)acrylamide, vinyl alcohol, allyl alcohol, and combinations thereof.
[0272] 61. The method or contact lens of any one of embodiments 40 to 60, wherein the at least one hydrophilic vinyl monomer comprises a methylene-containing pyrrolidone monomer selected from the group consisting of 1-methyl-3-methylene-2-pyrrolidone, 1-ethyl-3-methylene-2-pyrrolidone, 1-methyl-5-methylene-2-pyrrolidone, 1-ethyl-5-methylene-2-pyrrolidone, 5-methyl-3-methylene-2-pyrrolidone, methyl-2-pyrrolidone, 5-ethyl-3-methylene-2-pyrrolidone, 1-n-propyl-3-methylene-2-pyrrolidone, 1-n-propyl-5-methylene-2-pyrrolidone, 1-isopropyl-3-methylene-2-pyrrolidone, 1-isopropyl-5-methylene-2-pyrrolidone, 1-n-butyl-3-methylene-2-pyrrolidone, 1-tert-butyl-3-methylene-2-pyrrolidone, and combinations thereof.
[0273] 62. The method or contact lens of any one of embodiments 40 to 61, wherein the silicone hydrogel comprises repeating units of at least one UV absorbing vinylic monomer, and optionally repeating units of at least one UV / HEVL absorbing vinylic monomer.
[0274] 63. The method or contact lens of any one of embodiments 40 to 62, wherein the silicone hydrogel material has an equilibrium water content of about 10% to about 80% by weight.
[0275] 64. The method or contact lens of any one of embodiments 40 to 63, wherein the silicone hydrogel material has an oxygen permeability of about 50 barrer to about 180 barrer.
[0276] 65. The method or contact lens of any one of embodiments 40 to 63, wherein the silicone hydrogel material has an oxygen permeability of about 60 barrer to about 180 barrer.
[0277] 66. The method or contact lens of any one of embodiments 40 to 63, wherein the silicone hydrogel material has an oxygen permeability of about 70 barrer to about 180 barrer.
[0278] 67. The method or contact lens of any one of embodiments 40 to 63, wherein the silicone hydrogel material has an oxygen permeability of about 80 barrer to about 180 barrer.
[0279] 68. The method of any one of embodiments 1-15 and 19-67 or the contact lens of any one of embodiments 16-67, wherein the contact lens has a water break-up time of at least 12.5 seconds.
[0280] 69. The method of any one of embodiments 1-15 and 19-67 or the contact lens of any one of embodiments 16-67, wherein the contact lens has a water break-up time of at least 15 seconds.
[0281] 70. The method of any one of embodiments 1-15 and 19-67 or the contact lens of any one of embodiments 16-67, wherein the contact lens has a water break-up time of at least 17.5 seconds.
[0282] 71. The method of any one of embodiments 1-15 and 19-67 or the contact lens of any one of embodiments 16-67, wherein the contact lens has a water break-up time of at least 20 seconds.
[0283] The above disclosure will enable one of ordinary skill in the art to practice the present invention. Various modifications, variations and combinations may be made to the various embodiments described herein. In order to enable the reader to better understand its specific embodiments and advantages, it is recommended to refer to the following examples. The description and examples are intended to be considered exemplary.
[0284] Example 1
[0285] Oxygen permeability measurement
[0286] Unless otherwise specified, the oxygen permeability (Dk / t), intrinsic (or edge-corrected) oxygen permeability (Dk i or Dk c ).
[0287] Finger rubbing treatment
[0288] Use the lens The multifunctional lens care solution (or another multifunctional lens care solution) is rubbed with fingers (wearing disposable powder-free latex gloves) for 20 seconds and then rinsed with saline. The above procedure is repeated i times (i.e., i finger rubbing cycles) to simulate daily cleaning in an i-day lens care regimen, for example 7 times (i.e., 7 finger rubbing cycles) to simulate daily cleaning and disinfection in a 7-day lens care regimen), or 30 times (i.e., 30 finger rubbing cycles) to simulate daily cleaning and disinfection in a 30-day lens care regimen.
[0289] Lubricity evaluation.
[0290] The lubricity of contact lenses was evaluated by using a finger feel lubricity test, which qualitatively characterizes the slipperiness of the lens surface on a friction rating scale of 0 to 4. The higher the friction rating, the lower the slip (or lubricity).
[0291] Commercial lenses: OASYS TM ; ADVANCE PLUS TM ; Aqua Comfort and AIR They were respectively assigned friction grades (hereinafter indicated as "FR") of 0, 1, 2, 3, and 4. They were used as standard lenses for determining the friction grades of the lenses under test.
[0292] The samples were placed in PBS for at least two rinses for 30 minutes each and then transferred to fresh PBS before evaluation. Before evaluation, hands were rinsed with soap solution, rinsed thoroughly with DI water and then washed with water. Towel dry. Handle the samples between fingers and assign each sample a numerical value relative to the above standard lens described above. For example, if a lens is determined to be only slightly better than AIR lenses, they are assigned the number 3. The value of the Friction Grade is the value obtained by averaging the results of at least two Friction Grades of contact lenses by two or more persons and / or by averaging the Friction Grades of two or more contact lenses (from the same batch of lens production) by one person.
[0293] The digital lubricity (i.e., friction rating) of contact lenses can be determined according to the procedure described above: directly out-of-pack (OOP) but after soaking in PBS for ≥30 min or after i cycles (e.g., 7, 14, 21 or 30 cycles) of digital rubbing treatment or after simulated wear cycle treatment.
[0294] Surface wettability test
[0295] The water contact angle (WCA) on a contact lens is a general measure of the surface wettability of a contact lens. In particular, a low water contact angle corresponds to a more wettable surface. The average contact angle (sessile drop method) of a contact lens was measured using a VCA 2500XE contact angle measuring device (from AST, Inc., Boston, Massachusetts). This device is capable of measuring the advancing contact angle (θ a ) or receding contact angle (θ r ) or fixed (static) contact angle. Unless specified, the water contact angle is the fixed (static) contact angle of the front surface of the contact lens. The measurement is performed on a fully hydrated contact lens and immediately after blotting. The blotted lens is then mounted on a contact angle measurement support with the front surface facing up, and the sessile drop contact angle is automatically measured using the software provided by the manufacturer. The deionized water (ultrapure) used to measure the water contact angle has a resistivity of >18 MΩcm and the drop volume used is 2 μl. Before initiating contact with the contact lens, the tweezers and base are thoroughly washed with isopropyl alcohol and rinsed with DI water (deionized water). Each static water contact angle is the average of the left and right water contact angles. The static water contact angle for a contact lens is the average water contact angle obtained by averaging the static water contact angles measured with at least 5 contact lenses.
[0296] Water Breakdown Time (WBUT) Test
[0297] The surface hydrophilicity of the lens (after autoclaving) was evaluated by measuring the time required for the water film on the lens surface to begin to break up. Lenses exhibiting a WBUT ≥ 10 seconds were considered to have a hydrophilic surface and were expected to exhibit adequate wettability (ability to support a tear film) on the eye.
[0298] Lenses were prepared for water breakage measurements by removing the lens from its blister (Menicon) with soft plastic tweezers and placing the lens in a beaker containing phosphate buffered saline. The beaker contained at least 20 mL of phosphate buffered saline per lens, with a maximum of 3 lenses per beaker. The lenses were soaked for a minimum of 30 minutes and a maximum of 24 hours before being transferred to a 96-well plastic tray with fresh phosphate buffered saline using soft plastic tweezers.
[0299] The water break-up time (WBUT) is measured at room temperature as follows: Pick up the lens with soft plastic tweezers as close to the edge of the lens as possible, with the base curve facing the gauge, taking care not to touch the sides of the hole after the lens is removed from the saline. Shake the lens under test once to remove excess saline and start a timer. Ideally, the water film in the base curve surface of the lens will recede from the point of contact with the tweezers tip in a uniform circular pattern. When approximately 30% of the hydrated area recedes, stop the timer and record this time as the water break-up time (WBUT). Lenses that do not show an ideal receding pattern can be placed back in the dish and remeasured after rehydration for at least 30 seconds.
[0300] Balanced water content
[0301] The equilibrium water content (EWC) of a contact lens is determined as follows.
[0302] The amount of water (expressed as a weight percentage) present in a fully hydrated hydrogel contact lens equilibrated in saline solution at room temperature is determined using an analytical balance. The lenses are removed from the saline, quickly blotted dry with a wipe, stacked, and then transferred to an aluminum pan of pre-recorded weight. The number of lenses used for each sample pan is typically five (5). The hydrated weight of the pan plus the lenses is recorded. Cover the pan with aluminum foil. Place the pan in a laboratory oven at 100°C ± 2°C and dry for 16-18 hours. Remove the pan plus the lenses from the oven and cool in a desiccator for at least 30 minutes. Remove the pan from the desiccator and remove the aluminum foil. Weigh the pan plus the dried lens sample on an analytical balance. The dry and wet weights of the lens sample can be calculated by subtracting the empty pan weight, and the EWC is calculated by dividing the weight loss by the number of lenses.
[0303] Elastic modulus
[0304] The elastic modulus of contact lenses was determined using an MTS insight instrument. The contact lenses were first cut into 3.12 mm wide bands using a Precision Concept two-stage cutter. Five thickness values were measured over a 6.5 mm gauge length. The band was mounted on the instrument fixture and immersed in PBS, where the temperature was controlled at 21°C ± 2°C. Typically, a 5N load cell is used for testing. The fixture is separated at a constant speed until the sample breaks. Force and displacement data are collected by TestWorks software. The elastic modulus value is calculated by TestWorks software, which is the slope or tangent of the stress versus strain curve close to zero elongation in the elastic deformation region.
[0305] Low pH staining test
[0306] The integrity of the hydrogel coating on the contact lens can be determined based on the Nile red staining test.
[0307] Prepare Nile Red stock solution by dissolving 25 mg of Nile Red dye in 250 mL of 1-propanol. Dilute the Nile Red stock solution with n-heptane at a ratio of 1:20 to prepare Nile Red solution.
[0308] The contact lenses to be tested were first immersed in aqueous HCl (0.1 N) for 30 seconds, then removed from the HCl solution and immersed in Nile Red solution for 2 seconds, and finally removed from the Nile Red solution and immersed in USP purified water while agitating for 30 to 60 seconds to rinse off excess Nile Red solution. A Nile Red solution (12.5 μg / mL) in n-heptane was prepared by diluting 250 μL of Nile Red stock solution (250 μg / mL) in 1-propanol with 4750 μL of n-heptane.
[0309] Remove the lens from the blister. Gently tap the lens on a blotting cloth to remove excess saline remaining on the lens. Place the lens in a 0.1N HCl (aqueous) solution for 30 seconds. Remove the lens and gently tap the lens on a blotting cloth to remove excess HCl solution. Place in Nile Red solution for 2 seconds. Remove the lens and gently tap the lens on a blotting cloth to remove excess Nile Red solution. Place the lens in DI water for at least 30 seconds to rinse off excess Nile Red solution. Fill the lens sample holder with DI water and place the lens in the holder. Add additional DI water on top of the lens. Place a coverslip above the water meniscus. Place the lens sample holder in the sample chamber.
[0310] The contact lens is illuminated with blue light of 470nm wavelength to excite fluorescence. Nile red dye attaches itself to the hydrophobic area on the lens surface. The less red light emitted from the lens, the less Nile red dye, and the better the hydrophilic coating. The image of the fluorescence is recorded by a camera with a filter that blocks the excitation light and only allows light of the fluorescence wavelength to pass. Therefore, the area with an incomplete hydrogel coating appears bright orange in the fluorescence image. If no staining is observed at all, there are small spots of light orange, or a small number of small spots or small areas with low concentration orange, the test is indicated to be "passed" (i.e., the hydrogel coating on the contact lens is intact). If all staining is observed to be strong orange, a large number of bright strong orange areas and spots even have more black areas than orange areas at the same time, a large number of dark orange areas and spots have equal black and orange areas at the same time, or a large number of dark orange areas and spots have less black areas than orange areas at the same time, the test is indicated to be "failed" (i.e., the hydrogel coating on the contact lens is incomplete).
[0311] As controls, silicone hydrogel contact lenses without any coating and silicone hydrogel contact lenses with a base coating (a layer of polyacrylic acid or polymethacrylic acid) were also tested. Since these contact lenses in the control experiments did not have a hydrogel coating on them, Nile red could penetrate into the bulk silicone hydrogel material of the contact lenses. They would not pass the Nile red staining test.
[0312] Chemicals
[0313] The following abbreviations are used in the following examples: MPC represents 2-methacryloyloxyethyl phosphorylcholine; PEGMA300 represents polyethylene glycol methacrylate with a number average molecular weight of 300; APMAm represents N-(3-aminopropyl) methacrylamide; GMA represents glycidyl methacrylate; DMA represents N,N-dimethylacrylamide; CE-PDMS represents polysiloxane vinyl crosslinker (Mw is about 11-12 KDa, composed of H 1 NMR spectroscopy), having three polydimethylsiloxane (PDMS) segments connected via a diurethane bond between two PDMS segments and two urethane bonds each between a terminal methacrylate group and a PDMS segment, and prepared according to a method similar to that described in Example 2 of U.S. Pat. No. 9,315,669; TRIS-Am represents N-[tris(trimethylsiloxy)-silylpropyl]acrylamide; Vazo-56 represents 2,2'-azobis(2-amidinopropane) dihydrochloride; Vazo-64 represents 2,2'-dimethyl-2,2'azobispropionylnitrile; Norbloc is 2-[2'-hydroxy-5'-(2-methacryloyloxyethyl)phenyl)]-2H-benzotriazole; UV28 is 2-(3' -tert-butyl-2'-hydroxy-5'-(3"-methacryloxypropoxy)phenyl)-5-chloro-2H-benzotriazole; PAA denotes polyacrylic acid; poly(AA-co-Am) (10 / 90) denotes a copolymer of acrylic acid (AA, 10 mol%) and acrylamide (Am, 90 mol%); PAE denotes polyamidoamine-epichlorohydrin; DI water denotes deionized water; EtOH denotes ethanol; PrOH denotes 1-propanol; MEK denotes methyl ethyl ketone; PBS denotes phosphate buffered saline having a pH of 7.2±0.2 at 25°C and containing about 0.044 wt.% NaH2PO4·H2O, about 0.388 wt.% Na2HPO4·2H2O, and about 0.79 wt.% NaCl; and wt.% denotes weight percentage.
[0314] Example 2
[0315] Preparation of hydrophilic copolymers
[0316] 20.19g MPC and 20.24g PEGMA300 are dissolved in 100mL water. 5.01g APMAm is dissolved in 25mL DI water. 5.023g GMA is dissolved in 75mL DI water and 45g EtOH. 0.1342g Vazo-56 is dissolved in 5mL DI water. All solutions prepared above are added to 1L jacket reactor. 200mL DI water is rinsed in the container, and the rinse water is added to the reactor. The solution is purged with nitrogen at a flow rate of about 100mL / min for 10-12 minutes. After purging is completed, continue to cover with nitrogen at a flow rate of about 50 ml / min in the whole polymerization process. Through 2 hours, the solution temperature is ramped up to 53°C from room temperature, and this temperature is maintained for 10 hours. Purification by ultrafiltration (10kDa) uses 4 times of bed volumes to remove residual monomers.
[0317] Gelation studies:
[0318] To demonstrate the self-crosslinking ability, the above prepared hydrophilic copolymer (containing both epoxy and primary amino groups) was concentrated to 6.6% solids in water by rotary evaporation. The measured pH was 6.5. The sample was divided into a control and two experimental samples (A and B). Sample A had a pH of 6.5 (original pH), and sample B was brought to a pH of about 8.5 by adding 3N NaOH. Samples A and B were autoclaved for 45 minutes. The results are reported in Table 1. The increase in viscosity indicates intermolecular and intramolecular crosslinking of the hydrophilic copolymer.
[0319] Table 1
[0320] Comparison Sample A Sample B pH 6.5 6.5 8.5 Autoclave (45 min. and 121°C) no yes yes Viscosity(cps) 113 132 181 Remark Partial gel
[0321] A second gel study was conducted. 5 wt% PAA (M w 450KD) aqueous solution was mixed with a 5wt% aqueous solution of the prepared hydrophilic copolymer adjusted to pH 7. After the solutions were mixed, gelation occurred immediately. A portion of the formed gel was taken out and placed in excess water. The gel did not dissolve. This result shows the intermolecular and intramolecular crosslinking of PAA and the hydrophilic copolymer.
[0322] Example 3
[0323] Preparation of phosphate buffered saline
[0324] Phosphate buffered saline was prepared by dissolving 0.044 wt% NaH2PO4.H2O, 0.388 wt% Na2HPO4.2H2O, and 0.79% NaCl in DI water.
[0325] Preparation of 0.44% PAA solution
[0326] 0.88 g poly(acrylic acid) (PAA, M w About 450KD) was dissolved in 191.66g 1-propanol. 7.46g formic acid was added and mixed until the solution was homogeneous.
[0327] Preparation of IPC saline
[0328] In-package cross-linked packaging saline ("IPC saline") was prepared according to the procedure described in Example 19 of US 8480227. The prepared IPC saline contained a partially cross-linked and thermally cross-linkable hydrophilic polymer material produced in an additional step, namely, preheating PBS saline (pH 7.2-7.4) containing 0.07 wt% poly(Aam-co-AA) (90 / 10) Mw 200KD and 0.15 wt% PAE.
[0329] Preparation of Packaging Brine
[0330] Three packaging salines ("Salines") were prepared as follows to provide hydrophilic copolymer (prepared in Example 2) concentrations of 0.1 wt% (Saline A), 0.5 wt% (Saline B), and 2.0 wt% (Saline C). Purified copolymer solutions (6.6% solids, prepared in Example 2) were weighed into 20 mL scintillation vials. The remaining reagents were added in the appropriate amounts to the vials and mixed until completely dissolved, as shown in Table 2.
[0331] Table 2
[0332]
[0333] Preparation of lens formulations
[0334] A lens formulation was prepared to have the following composition: 10 parts by weight of PrOH; 32 parts by weight of DMA; 1.5 parts by weight of Norbloc; 0.4 parts by weight of UV28; 28 parts by weight of TRIS-Am; 40 parts by weight of CE-PDMS; and 0.5 parts by weight of Vazo-64. All components were added to a clean bottle and mixed with a stir bar at 600 rpm for 30 minutes at room temperature. After all solids were dissolved, the formulation was filtered with a glass microfilter (2.7 μm GMF filter).
[0335] Lens manufacturing
[0336] The lens is prepared by cast molding from the lens formulation prepared above. The lens formulation is purged with nitrogen at room temperature for 30 to 35 minutes. The N2-purged lens formulation is introduced into a polypropylene mold. The mold with the lens formulation therein is placed in an oven with room temperature, and the oven is N2-purged for 30 minutes. The mold with the lens formulation therein is placed in an oven with room temperature. Then, the oven is N2-purged for 30 minutes, and then a thermal curing process is performed according to a curing curve (heating from room temperature to 110°C at a ramp rate of about 5°C / min and directly cooling).
[0337] The lens molds, each having a molded silicone hydrogel lens precursor therein, are mechanically opened. The molded silicone hydrogel precursor adheres to the male mold half and is removed (ie, "delensed") from the male mold half to which the lens adheres using liquid nitrogen.
[0338] After delensing, the SiHy lens precursors prepared above were subjected to the following post-molding steps (ie, the SiHy lens precursors were immersed in a series of different solution baths), as shown in Table 3.
[0339] Table 3
[0340] Dipping step solution bath Immersion time(s) 1 MEK 22 2 MEK 78 3 MEK 224 4 DI water 56 5 0.44% PAA solution 56 6 50 / 50 1-PrOH / DI water 56 7 DI water 56 8 DI water 56 9 DI water 56 10 DI water 56 11 PBS Keep
[0341] The SiHy contact lens has the following properties: Dkc about 140 barrer; EWC about 32 wt.%; elastic modulus about 0.79 MPa.
[0342] Application of cross-linked hydrophilic coatings (hydrogel coatings)
[0343] After the above post-molding steps, the resulting SiHy contact lenses were placed individually in polypropylene lens packaging shells (or blisters) (one lens per shell), each shell containing 0.65 mL of Saline A, Saline B, Saline C, PBS or IPC saline. The blisters were then sealed with foil and autoclaved at about 121° C. for about 45 minutes.
[0344] Lens test:
[0345] After autoclaving, the coated SiHy contact lenses were evaluated by low pH CLAN to test for the presence of a uniform cross-linked lens surface coating. The negative control (without any hydrogel coating thereon) failed the test, while the positive control (with a hydrogel coating thereon) and the 3 tested lenses passed the test, indicating the presence of a cross-linked uniform surface coating (hydrogel coating). The coated SiHy contact lenses were also subjected to a manual rubbing cycle to evaluate the durability of the hydrogel coating. These tested lenses still passed the low pH CLAN test, indicating that the hydrogel coating has some durability. The finger lubricity test indicated that the lubricity of the lens surface was also good.
[0346] Table 4
[0347]
[0348] All publications, patents, and patent application publications cited herein above in this application are hereby incorporated by reference in their entirety.
Claims
1. A method for preparing a coated contact lens, the method comprising the steps of: (1) obtaining a contact lens precursor having a concave surface and an opposite convex surface and comprising a lens bulk material and carboxylic acid groups on and / or near the anterior and posterior surfaces; (2) immersing the contact lens precursor in an aqueous solution in a container, wherein the aqueous solution comprises from about 0.01% to about 5.0% by weight of at least one hydrophilic copolymer comprising (a) monomer units of at least one vinyl monomer containing an epoxy group, (b) monomer units of at least one vinyl monomer containing an amino group having a primary or secondary amino group, (c) monomer units of at least one vinyl monomer containing polyethylene glycol, and (d) monomer units of at least one vinyl monomer containing phosphorylcholine, wherein the sum of the amounts of components (a) and (b) in the at least one hydrophilic copolymer is about 40% or less by mole; and (3) heating the aqueous solution having the contact lens precursor therein at a temperature of about 100° C. to about 140° C. for at least 30 minutes to form a coated contact lens having a hydrogel coating thereon, wherein the hydrogel coating is covalently attached to the anterior surface and the posterior surface via bonds each formed between one carboxylic acid group and one epoxy group, wherein the hydrogel coating comprises a cross-linked polymer material comprising polymer chains derived from the hydrophilic copolymer, wherein the contact lens has a water break up time (WBUT) of at least 10 seconds.
2. The method of claim 1, wherein: The contact lens precursor is comprised of a lens bulk material having carboxylic acid groups on and / or near the surface of the lens bulk material.
3. The method of claim 2, wherein: The lens bulk material is obtained by polymerizing a polymerizable composition comprising from about 0.1% to about 10% by weight of a vinyl monomer, the vinyl monomer further comprising at least one carboxylic acid group.
4. The method of claim 2, wherein: The lens bulk material has been subjected to at least one post-cure surface treatment to have the carboxylic acid groups on and / or near the surface of the lens bulk material.
5. The method of claim 1, wherein: The contact lens precursor comprises a lens bulk material and a layer of at least one polymer material having carboxylic acid groups thereon.
6. The method of claim 5, wherein: The at least one polymer material having a carboxylic acid group includes a homopolymer or a copolymer of acrylic acid or a C1-C3 alkyl acrylic acid.
7. The method according to any one of claims 1 to 6, wherein: The heating step is performed by autoclaving the contact lens precursor having the carboxylic acid groups thereon immersed in the aqueous solution which is the packaging solution in the sealed lens package at a temperature of about 115°C to about 125°C for about 30-90 minutes.
8. A contact lens comprising: a front surface, an opposite back surface, and a layered structure configuration from the front surface to the back surface, wherein the layered structure configuration includes an outer front surface hydrogel layer, an inner layer, and an outer back surface hydrogel layer, wherein the inner layer includes a lens bulk material and has carboxylic acid groups on and / or near the surface of the inner layer, wherein the outer front surface hydrogel layer and the outer back surface hydrogel layer include a cross-linked polymer material, the cross-linked polymer material includes polymer chains derived from a hydrophilic copolymer, the hydrophilic copolymer including (a) at least one monomer unit of an epoxy-containing vinyl monomer, (b) at least one The invention relates to a hydrophilic copolymer comprising: (a) a monomer unit of at least one amino group-containing vinyl monomer having a primary or secondary amino group, (c) a monomer unit of at least one vinyl monomer containing polyethylene glycol, and (d) a monomer unit of at least one vinyl monomer containing phosphorylcholine, wherein the sum of the amounts of components (a) and (b) in the at least one hydrophilic copolymer is about 40% or less by mole, wherein the outer front surface hydrogel layer and the outer back surface hydrogel layer are covalently attached to the inner layer through bonds each formed between one carboxylic acid group and one epoxy group, wherein the contact lens has a water break up time (WBUT) of at least 10 seconds.
9. The contact lens of claim 8, wherein: The inner layer is composed of a lens bulk material having carboxylic acid groups on and / or near the surface of the lens bulk material.
10. The contact lens of claim 8, wherein: The inner layer comprises a layer of lens bulk material and at least one polymer material having carboxylic acid groups, wherein the at least one polymer material having carboxylic acid groups comprises a homopolymer or copolymer of acrylic acid or C1-C3 alkyl acrylic acid.
11. The method of any one of claims 1 to 7 or the contact lens of any one of claims 8 to 10, wherein: The at least one hydrophilic copolymer comprises: (a) at least one having the formula Monomer units of epoxy-containing vinyl monomers; (b) at least one having the formula Monomer units of amino-containing acrylic monomers; (c) at least one having the formula Monomer units of acrylic monomers containing polyethylene glycol; as well as (d) at least one having the formula The monomer unit of the phosphorylcholine-containing acrylic monomer, in: Each R0 is independently H or CH3; each R0' is independently H or C1-C4 alkyl; B1, B2 and B3 are independently O or NR'; R' is H or C1-C4 alkyl; D1, D2 and D3 are independently C1-C 12 Alkylene divalent group; D0 is C1-C 12 An alkylene divalent group or a divalent group of -D4-O-D5-B4-CH2-; B4 is -O- or D4 is C1-C 12 Alkylene divalent group; D5 is a C2-C6 alkylene divalent group or D6 and D7 are independently C2-C6 alkylene divalent groups; d1 is 0, 1 or 2; PEG is A polyethylene glycol group, wherein R" is H or a C1-C4 alkyl group; t2 is an integer from 3 to 100; PC is A zwitterionic group, wherein t1 is an integer from 1 to 5, and 1 R. 2 R and 3 R is independently C1-C8 alkyl or C1-C8 hydroxyalkyl.
12. The method of any one of claims 1 to 7 or the contact lens of any one of claims 8 to 10, wherein: The at least one hydrophilic copolymer is a statistical copolymer having formula (I) in T' and T" are independently H or a terminal group; each R0 is independently H or CH3; each R0' is independently H or a C1-C4 alkyl group; B1, B2 and B3 are independently O or NR'; R' is H or a C1-C4 alkyl group; D1, D2 and D3 are independently C1-C 12 Alkylene divalent group; D0 is C1-C 12 An alkylene divalent group or a divalent group of -D4-O-D5-B4-CH2-; B4 is -O- or D4 is C1-C 12 Alkylene divalent group; D5 is a C2-C6 alkylene divalent group or D6 and D7 are independently C2-C6 alkylene divalent groups; d1 is 0, 1 or 2; PEG is A polyethylene glycol group, wherein R" is H or a C1-C4 alkyl group; t2 is an integer from 3 to 100; PC is A zwitterionic group, wherein t1 is an integer from 1 to 5, and 1 R. 2 R and 3 R is independently a C1-C8 alkyl group or a C1-C8 hydroxyalkyl group; a, b, c, and d are independently an integer from 5 to 100, wherein (a+c) / (a+b+c+d)≤0.
40.
13. The method of any one of claims 1 to 7, 11 and 12 or the contact lens of any one of claims 8 to 12, wherein: The lens body material is (i) a hard plastic material, (ii) a rigid gas permeable lens material, (iii) a non-silicone hydrogel material, or (iv) a silicone hydrogel material.
14. The method of any one of claims 1 to 7, 11 and 12 or the contact lens of any one of claims 8 to 12, wherein: The lens body material consists essentially of: (a) a central optical zone, which is essentially made of a rigid gas permeable lens material and is surrounded by a peripheral zone essentially made of a silicone hydrogel material, or (b) a 3-dimensional article and a silicone hydrogel material, wherein the 3-dimensional article is made of a non-hydrogel material and has a smaller 3-dimensional size than a preformed embedded contact lens so that the 3-dimensional article is completely embedded in the silicone hydrogel material.
15. The method of any one of claims 1 to 7, 11 and 12 or the contact lens of any one of claims 8 to 12, wherein: The lens body material consists essentially of: (a) a central optical zone, which is essentially made of a rigid gas permeable lens material and is surrounded by a peripheral zone essentially made of a non-silicone hydrogel material, or (b) a 3-dimensional article and a non-silicone hydrogel material, wherein the 3-dimensional article is made of a non-hydrogel material and has a smaller 3-dimensional size than a preformed embedded contact lens so that the 3-dimensional article is completely embedded in the non-silicone hydrogel material.
Citation Information
Patent Citations
Contact lens and its production
JP2001075060A
Hydrophilized polydiorganosiloxane vinylic crosslinkers and uses thereof
US10081697B2
Ophthalmic devices for delivery of hydrophobic comfort agents
US10155349B2
UV-absorbing vinylic monomers and uses thereof
US10254567B2
Weekly and monthly disposable water gradient contact lenses
US11256003B2